Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that it increases knowledge acquisition rates, enhances information flow among policy actors, and provides opportunities for creating shared understandings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that scientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays inadequate attention to policy processes that promote the development of shared understandings among diverse stakeholders. To be effective, new adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support new forms of cooperation among stakeholders.

Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to integrate knowledge and make predictions. The term has since become increasingly widely used in scientific articles, policy documents and management plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natural resource management journals to assess diversity in how the term is used, highlight ambiguities and consider how the concept might be further assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management outcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Significant confusion exists over the distinction between active and passive approaches. Over half of the studies reporting to implement AM claimed to have done so successfully, yet none quantified specific benefits, or costs, in relation to possible alternatives. Similarly those studies reporting to assess the approach did so only in relation to specific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resources, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly accurate. From a scientific and technical perspective many practical questions remain; in particular real-world assessments of the value of experimentation within a management framework, as well as of identified challenges and pathologies, are needed. Further discussion and systematic assessment of the approach is required, together with greater attention to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty

Adaptive management intentions with a reality of evaluation: Getting science back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of water to irrigation with the use of water for environmental outcomes. However, in many aspects, scientific knowledge of the environment is either imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of political arguments. In response to uncertainty and knowledge gaps, adaptive management has been written into the legislation, along with provisions for periodic evaluation. This research ascertains how adaptive management is understood by policy makers, with this indicative of future implementation of adaptive management. The way in which adaptive management is constructed by policy makers is determined through legislation, public speeches, government reports and semi-structured interviews. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, with the dominance of evaluation discussed as limiting innovation and reinforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty

Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Getting intentional about M&E: choosing suitable approaches for adaptive programmes - Management, Global Learning for Adaptive (GLAM Blog, 2020)
Does the choice of monitoring and evaluation (M&E) approaches and tools matter for adaptive programmes? In short, yes: monitoring, evaluation and learning (MEL) and adaptive management (AM) are intertwined. While programme monitoring data and evaluation results are not the only sources of evidence that programmes use for learning and iteration, they often are amongst most important ones — or at least they should be. Selecting what type of information to collect and analyse — and how — is critical for any type of programme. However, what AM especially focuses on is intentionally building in opportunities for structured and collective reflection, ongoing and real-time learning, course correction and decision-making in order to improve effectiveness.

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam Research Reports, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Managing Complexity: Adaptive Management at Mercy Corps - Mercy Corps (2015)
Managing Complexity: Adaptive management at Mercy Corps

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.

Is the problem driven iterative adaptation approach (PDIA) a panacea for public financial management reform? Evidence from six African countries - Lawson, Andrew; Harris, Jamelia (World Development Perspectives, 2023)
This article assesses the application of the problem driven iterative adaptation (PDIA) approach to public financial management reform in six African countries. It draws on primary data collected using a mix of interviews, overt participation observations and a short survey. PDIA responds to shortcomings in orthodox approaches to reform and technical assistance in developing countries. It stresses local solutions to local problems, achieved through experimentation and adaptation. The principles of PDIA are appealing, but its empirical assessment is in its infancy. This study aims to fill part of this gap. Findings show that PDIA delivers results in the short-term, particularly in cases where there is an influential authorising agent and dedicated team. Progress was less forthcoming for reforms that required high level political buy-in from senior officials. The approach does exceptionally well to develop staff capability, transferable skills, and local empowerment to solve local problems, thus potentially benefitting future reforms.

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Project facilitation as an active response to tensions in international development programmes - Lannon, John; Walsh, John N. (International Journal of Project Management, 2020)
This paper examines the tension within international development programmes between traditional task-oriented approaches to development and the wider view of programmes as sites for adaptability and learning. It characterises it as a set of inter-related tensions between recursive and adaptive tendencies that exist at individual actor, programme and institutional levels. Drawing on a multiple interpretive case study of partnership based programmes between an international non-government organisation and local partners in three countries, it looks at how these tensions play out in practice. Based on the findings, it proposes an active response to the tensions called project facilitation. This is an adaptive and co-created process that incorporates local experience and practice based knowledge to achieve strategic goals, while utilising recognised project management practices to achieve agreed outcomes. By adopting active responses to the tensions that exist within programmes it offers greater potential for effective delivery of long term benefits than the more typical defensive response strategies. Project facilitation is consistent with the social constructionist view of programmes and programme management but broadens our understanding by emphasising the need to actively consider how the tensions inherent in programmes are responded to.
Keywords: Adaptive management; International development; Non-governmental organisations; Partnership; Programme management; Project facilitation; Tensions

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Reacting or adapting? Purposeful adaptation and response to contextual change. - Wood, Nik (Rebel with Causation, 2020)
Adaptive management is increasingly on the ticket for development programming, and has been crucial in the wake of covid-19. I’ve been working with adaptive programmes for most of my career, …

Adapting to Learn and Learning to Adapt: Practical Insights from International Development Projects - Brinkerhoff, Derick W.; Frazer, Sarah; McGregor, Lisa (RTI Press, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning, and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle. It both erases the boundaries between design, implementation, and evaluation and reframes thinking to consider the complexity of development problems and nonlinear change pathways.Supportive management structures and processes are crucial for fostering adaptive management. Implementers and donors are experimenting with how procurement, contracting, work planning, and reporting can be modified to foster adaptive programming. Well-designed monitoring, evaluation, and learning systems can go beyond meeting accountability and reporting requirements to produce data and learning for evidence-based decision making and adaptive management. It is important to continue experimenting and learning to integrate adaptive programming and management into the operational policies and practices of donor agencies, country partners, and implementers. We need to devote ongoing effort to build the evidence base for the contributions of adaptive management to achieving international development results.

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

Learning to ADAPT: monitoring and evaluation approaches in climate change adaptation and disaster risk reduction – challenges, gaps and ways forward - Silva Villanueva, Paula (SRC Discussion Paper, 2011)
This working paper is a methodological contribution to the emerging debate on monitoring and evaluation (M&E) in the context of climate change adaptationand disaster risk reduction. Effectively managing disaster risk is critical for adapting to the impacts of climate change, however disasters risk reduction M&E practice may be limited in capturing progress towards adaptation. The unique nature of adaptation to climate change calls for experience-based learning M&E processes for discovering the key insights into adaptive capacity and its links to adaptation processes, and to risk and vulnerability reduction at large. The ADAPT guiding principles and indicators set the foundations towards this end.

(Re)making the case for adaptive management - Aston, Thomas (Medium, 2022)
Great overview of what to read on adaptive management. It’s a long one, so I’ve split it into two – second installment tomorrow. Christian Aid Ireland’s recent publication The Difference Learning Makes by Stephen Gray and Andy Carl made a bit of a splash. The study found that Christian Aid Ireland’s application of adaptive programming contributed to better development outcomes and supported more flexible delivery. The much vaunted MUVA programme in Mozambique is also coming to a close and presenting its results from using and adaptive approach. So, it struck me that we might be at a critical juncture in the conversation on adaptive management. We’ve had the crashing to earth of inflated expectations in recent misanthropic reflections, [misanthropic, moi? – Duncan] alongside a fragile institutionalisation of adaptive management in donor agencies, NGOs, and private sector organisations. However, I’d argue that we’ve reached the point where adaptive management has passed the proof-of-concept stage.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Linking constituent engagement and adaptive management - Buell, Stephanie; Campbell, Megan; Pett, Jamie (Overseas Development Institute, 2020)
Constituent engagement is the two-way process of involving constituents in the design, delivery, monitoring and evaluation of programmes. Constituent engagement and adaptive management together can be a powerful combination; high-quality constituent engagement can reinforce effective adaptive management, and vice versa. By highlighting stories from leading practitioners and their organisations, this paper explores how programmes ensure that constituent engagement informs meaningful adaptation. Key messages Constituent engagement and adaptive management are both important tools for implementing responsive and effective development programmes. Together, they can be a powerful combination: input from constituent engagement can be a key source of information and evidence that meaningfully informs programme design and adaptation, and closing the feedback loop in this way increases the quality of future engagement. Both adaptive management and community engagement principles recognise that, for a programme to be effective, it must be responsive to the people meant to ultimately benefit from it. Beyond providing a key source of information for potential programme adaptations, constituent engagement efforts also help build trust with stakeholders, align expectations and promote accountability. This paper explores five key elements for ensuring that constituent engagement and adaptive management are effectively linked within a programme: strong internal systems and external channels; skilled staff that value engagement and adaptation; decision-maker champions; clear points for reflection and action; and a meaningful role for constituents.

Adaptive Management in International Development - Knowledge Base - Prieto Martin, Pedro (2025)
A curated collection of resources on Adaptive Management and MEL in International Development

Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning strategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Management programme will make available technical assistance to DFID, USAID and partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable development interventions.

Navigating complexity: Adaptive management in the Northern Karamoja Growth, Health & Governance program - Allana, Amir (MercyCorps, 2014)
Development actors increasing agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. But what does adaptive management look like in practice?
Keywords: IMPORTANT; Practice

Guidance Note for Adaptive Management - Ministry of Foreign Affairs of Denmark (Government of Denmark, 2022)
This note explains what adaptive aid management is; why and when it should be considered; and how it should be applied. It covers all Danish development support channels and modalities, including bilateral country assistance, assistance to and through civil society, the private sector and to and through multilateral organisations. This guide has three chapters. Chapter 1 provides an executive overview of what adaptive management is. Chapter 2 goes deeper into five key operational principles of adaptive management. Chapter 3 details the main tenets of adaptive management processes during the programming cycle.

Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (IDS Working Paper, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Toybox's Adaptive Management in Practice - Malcolm, Emily (Toybox, 2017)
At Toybox, we understand ‘Adaptive Management’ as a broad innovative and learning approach that involves the whole organisation, our partners and funders. ‘Adaptive Programming’ of projects is part of this approach which is greatly enhanced by the Adaptive Management of all actors, including communities and children in the projects. Over the last few years Toybox have been piloting Adaptive Programming with our partners across Latin America, Africa and Asia to support children in street situations. This project has been developed within the wider context of an organisation which is focused on innovation and learning, therefore enabling Adaptive Management to become mainstream within the organisation. This paper captures the experiences and learnings of Toybox to our newly implemented Adaptive Programming approach, through the lens of a small-sized UK-based organisation working with local organisations internationally. This paper explains our learnings, inclusive of why we believe Adaptive Management is important to Toybox and how the organisation has embraced this new approach.

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Adaptive Management - Bormann, B.T.; Martin, J.R.; Wagner, F.H.; Wood, G.W.; Alegria, J. (Ecological stewardship: a common reference for ecosystem management, 1999)
Wagner
Keywords: Conservation of natural resources; Ecology; Ecosystem management; Ecosystem management - United States; Environmental Science; Environmental management; Wildlife

Adaptive Management Leaders Launch Practical Adaptation Network (PAN) - Labs, Feedback (FeedbackLabs, 2016)
Great things can happen at the frontier of theory and practice. When Feedback Labs worked with USAID’s Global Development Lab to bring together leaders in adaptive management at the White House on June 15th, we were pleased that we were able to move past the ongoing conceptual conversations toward discussing what we could do in concrete terms to implement adaptive management in practice.

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Prospects practice paper, 1, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptive Management for International Development Programs - Loveridge, Donna (Australasian Evaluation Society Conference, 2007)
Capacity development, that is “the process whereby people, organisations and society as a whole unleash, strengthen, create, adapt and maintain capacity over time” (OECD 2005) has been a key aim of international aid programs. However, capacity development efforts have not met with resounding success despite approximately 25%, or USD15 billion a year, being spent by donors in recent years on technical assistance1 which has predominantly been aimed at developing capacity. A 1998 review by the World Bank (World Bank 1998) found that the success rate for capacity development efforts was between 30 – 40%. The Commission for Africa (2005) noted in 2005 that achievements were below expectations. The OECD (2007) sees capacity development as being one of the areas which are least responsive to development assistance and therefore one of the greatest challenges. This paper proposes that development practitioners and donors could benefit from taking an evaluative inquiry-type of approach to the design, implementation and monitoring and evaluation of capacity development programs. An alternative approach, “adaptive management”, is proposed. Adaptive management moves away from a rational linear A + B = C approach to capacity development towards constructing and testing theories of change2 for knowledge generation, adaptation and program improvement.

Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environments – when there is scope to trial and adapt programme strategies. So argues Amir Allana in Navigating Complexity, a case study of Northern Karamoja's Growth, Health and Governance (GHG) Programme that is adopting an 'adaptive management' approach. This BEAM Exchange webinar invited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from their work in Uganda and Cambodia. What does adaptive management look like in practice? And what does it require of managers and funders to make it happen? Tim and Peter share their experiences of applying adaptive management techniques to the Growth, Health and Governance Programme and the Cambodia Agricultural Value Chain Program (CAVAC). Amir highlight insights from the Navigating Complexity report, including the importance of office culture, consistent management signals, and the role of supportive tools and processes.

Doing adaptive management at Sida - Tim Ruffer; Helen Bailey; Stefan Dahlgren; Patrick Spaven; Mark Winters (Evaluation Brief, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures

Guidance Note: Practical introduction to adaptive management - DT Global (DT Global, 2022)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

Adapting data collection and utilisation to a Covid-19 reality: Monitoring, evaluation and learning approaches for adaptive management - Ziegler, Jessica; Mason, Paige (Briefing Paper, 2020)
This briefing note focuses on the remote collection and use of data for adaptive management during the Covid-19 pandemic, setting out key considerations to help practitioners think through a transition from more ‘traditional’ monitoring, evaluation and learning (MEL) to MEL for adaptive management (MEL4AM) that reflects the unique data collection challenges presented by Covid-19. The brief provides an overview of some key considerations in remote data collection, when this is required, and identifies other sources that address these issues in more detail. It concludes with a discussion of how to bring the information resulting from remote monitoring into decision-making to enable adaptive management. Key messages - When planning for remote data collection during the Covid-19 pandemic, first determine what information is still necessary, because data needs may have changed, e.g. if programming has pivoted or needs to pivot due to Covid-19. Then identify how the programme’s information needs align with existing data sources and what gaps remain, which will guide the need for remote data collection. - Also consider what data is ‘good enough’ for current decision-making needs in order to provide sufficient information to the right people at the right time to an acceptable standard of rigour. - There may be pragmatic reasons to reduce the number or scope of MEL activities, such as logistical constraints or ethical considerations introduced by the pandemic. - MEL activities should be accompanied by frequent feedback loops and pause points to reflect on emergent needs and challenges, information needs that have been met, and contextual changes that may affect MEL. - Be clear with decision-makers about the assumptions and gaps in the data, including proxies used and their limitations, sampling changes, and how these changes and assumptions may affect the decisions/options being discussed.

Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Contribution analysis for adaptive management - Apgar, Marina; Hernandez, Kevin; Ton, Giel (Briefing Paper, 2020)
This briefing note shares practical learning on the use of contribution analysis for adaptive management (CA4AM). It examines how the approach enables programmes to work with theories of change in a practical, reflexive way, and how, combined with assessing evidence of a programme’s contribution to change, its findings can inform programme adaptation. It also examines both how and to what extent CA enables AM through the experiences of four large complex programmes all working towards systems-level change and employing a structured process of reflection on theories of change. Key messages CA4AM can enable programmes to work with theories of change in a practical, reflexive way. It is particularly useful for programmes operating in conditions of complexity, when it is difficult to discern attribution and when systems-level change is the goal. A range of enabling factors help CA4AM to be used most effectively, including contractual flexibility; embedded monitoring, evaluation and learning (MEL); and supportive leadership.

Listen carefully. Tread lightly. Adapt quickly. Approaching Adaptive Management: Examples from our Somalia Education Programming - CARE (CARE Learning, 2020)
Adaptive management approaches potentially offer us opportunities to deliver high quality results in circumstances where change is complex, including in fragile, unstable or conflict affected places. However, building adaptive programming continues to be a challenge for the sector. For CARE, our Department for International Development -UK Aid funded Girls’ Education Challenge (GEC) programming has provided useful learning on how to operationalise adaptive approaches. In this paper we expand on our learning from this project and offer some recommendations for how to create more opportunities for truly adaptive programming in the future. In particular: • Projects that are designed to adapt need budget structures, results frameworks and governance that enable the process of adaptation. In our GEC projects the approaches employed by DFID, including the introduction of Review and Adaptation meetings have served to support meaningful adaptation. • Adaptive projects require both strong participatory elements and flexible governance and accountability structures. Whilst rigorous and comprehensive Monitoring, Evaluation and Learning (MEL) systems are important without these other elements appropriate adaptation can be hindered. • Adaptive Management requires resources. Where the expected change is complex, adaptation is frequently necessary to ensure we are responding to context and evidence. This should be adequately resourced if we are to expect results. In an environment where many INGOs work consistently within complex environments, the sector also needs more opportunities to trial these approaches and could benefit from more funding streams available which include the kinds of approaches used by DFID in current GEC programming

Lessons Learned From the Use of the Most Significant Change Technique for Adaptive Management of Complex Health Interventions - Ohkubo, Saori; Mwaikambo, Lisa; Salem, Ruwaida M.; Ajijola, Lekan; Nyachae, Paul; Sharma, Mukesh Kumar (Global Health: Science and Practice, 2022)
Introduction:The Most Significant Change (MSC) technique is a complex-aware monitoring and evaluation tool, widely recognized for various adaptive management purposes. The documentation of practical examples using the MSC technique for an ongoing monitoring purpose is limited. We aim to fill the current gap by documenting and sharing the experience and lessons learned of The Challenge Initiative (TCI), which is scaling up evidence-based family planning (FP) and adolescent and youth sexual and reproductive health (AYSRH) interventions in 11 countries in Asia and sub-Saharan Africa. Methods:The qualitative assessment took place in early 2021 to document TCI’s use and adaptation of MSC and determine its added value in adaptive management, routine monitoring, and cross-learning efforts. Focus group discussions and key informant interviews were conducted virtually with staff members involved in collecting and selecting MSC stories. Results:TCI has had a positive experience with using MSC to facilitate adaptive management in multiple countries. The use of MSC has created learning opportunities that have helped diffuse evidence-based FP and AYSRH interventions both within and across countries. The responsive feedback step in the MSC process was viewed as indispensable to learning and collaboration. There are several necessary inputs to successful use of the method, including buy-in about the benefits, training on good interviewing techniques and qualitative research, and dedicated staff to manage the process. Conclusion:Our assessment results suggest that the MSC technique is an effective qualitative data collection tool to strengthen routine monitoring and adaptive management efforts that allows for flexibility in how project stakeholders implement the process. The MSC technique could be an important tool for global health practitioners, policy makers, and researchers working on complex interventions because they continually need to understand stakeholders’ needs and priorities, learn from lessons and evidence-based practices, and be agile about addressing potential challenges.

Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (CLARISSA Research and Evidence Paper, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Adaptive Software Development: A Collaborative Approach to Managing Complex Systems - Highsmith, Jim (Dorset House Publishing, 2000)
In today's turbulent e-business world, software project teams that survive and thrive won't be those that continue their traditions of optimization, efficiency, and control, but those that exhibit adaptability, speed, and collaboration. Adaptive Software Development is targeted at software teams where competition creates extreme pressure on the delivery process. Four goals of the book are * to support an adaptive culture in which change and uncertainty are assumed to be the natural state * to introduce frameworks to guide the iterative process of managing change * to institute collaboration, the interaction of people on interpersonal, cultural, and structural levels * to add rigor and discipline to the RAD approach, making it scalable to the uncertainty and complexity of real-world undertakings. This innovative text, grounded in the science of complex adaptive systems theory, offers a practical, realistic approach to managing the high-speed, high-change projects characteristic of our highly uncertain economy.

Learning to Adapt: Building Adaptive Management as a Core Competency in Development Practice - Ramalingam, Ben (Institute of Development Studies, 2016)
Key messages 1. Development policies and programs increasingly operate in situations of high complexity and uncertainty. 2. There are growing efforts across the sector to design, plan and implement more adaptive responses that are more relevant and appropriate in such contexts 3. At the heart of effective adaptive programming is the capability to gather, interpret and use knowledge, information and data in real-time 4. Strengthening this capability requires a positive enabling environment—including tools and methods, structures and processes, leadership and management and culture and mindsets. 5. For adaptive development to succeed, there needs to be greater attention and investment in both knowledge, information and data systems and in appropriate enabling environments
Keywords: IMPORTANT

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Action for Empowerment and Accountability Research Programme, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

ADAPT: Analysis Driven Agile Programming Techniques - IRC (International Rescue Committee (IRC), 2016)
A growing body of research indicates that aid agencies are most successful when able to operate flexibly, particularly in fragile environments. Yet our systems and tools are often too rigid to effectively address complex problems, and program incentives frequently undermine adaptation instead of supporting it. To drive improvements in impact we need to be better able to analyse the dynamics of a given situation, anticipate how these might evolve, and be sufficiently agile to adapt to changes in context and need.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adaptive Action: Leveraging Uncertainty in Your Organization - Eoyang, Glenda H.; Holladay, Royce J. (Stanford University Press, 2013)
Rooted in the study of chaos and complexity, Adaptive Action introduces a simple, common sense process that will guide you and your organization into reflective action. This elegant method prompts readers to engage with three deceptively simple questions: What? So what? Now what? The first leads to careful observation. The second invites you to thoughtfully consider options and implications. The third ignites effective action. Together, these questions and the tools that support them produce a dynamic and creative dance with uncertainty. The road-tested steps of adaptive action can be used to devise solutions and improve performance across multiple challenges, and they have proven to be scalable from individuals to work groups, from organizations to communities. In addition to laying out the adaptive action framework and clear protocols to support it, Glenda H. Eoyang and Royce J. Holladay introduce best practices from exemplary professionals who have used adaptive action to meet personal, professional, and political challenges in leadership, consulting, Alzheimer's treatment, evaluation, education reform, political advocacy, and cultural engagement―readying readers to employ this new toolkit to meet their own goals with a sense of ingenuity and flexibility.

Adaptive development: great progress and some niggles - Vowles, Pete (Medium, 2016)
After 3 years in DFID headquarters, championing adaptive approaches to the delivery of aid and development programmes, I am back in an…

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.

Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Working Paper, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (CLARISSA Research and Evidence Paper, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.

Adaptive Programming: The “Space of Possibility” - Seavey, Sara Mizuta (USAID Learning Lab, 2016)
Sara Mizuta Seavey, M.A., is a Senior Program Officer at FHI360 for the Mobile Solutions Technical Assistance and Research (mSTAR) project, where she works with USAID’s Digital Development Team to conceive, design, and test how real-time data systems can enable a more adaptive and participatory approach to development. She is passionate about systems thinking and participatory approaches to international development. What does space travel have to do with international development?

Monitoring for problem-solving, adaptive management, reporting and learning - Dominique Morel; Dzino-Silajdzic, Velida; Hagens, Clara (Catholic Relief Services, 2020)
Internal and external stakeholders have different information needs over a project’s life, for purposes that include adaptive management, accountability, compliance, reporting and learning. A project’s monitoring, evaluation, accountability and learning, or MEAL, system should provide the information needed by these stakeholders at the level of statistical reliability, detail and timing appropriate to inform data use. In emergency contexts where the situation is still fluid, ‘informal monitoring’ has proved helpful to staff’s ongoing assessment of the broader environment in order to identify changes in the situation, in other actors’ responses, and in priority unmet needs that would require corresponding changes in the response.2 The same distinction between informal monitoring of possible changes in the project’s operating context—whether identified as project assumptions and risk factors or not—and formal monitoring of the activities included in the response and project indicators, is relevant for development contexts too. Informal monitoring: Ongoing assessment of changes in operating context Formal monitoring: Tracking progress against project activities and indicators Within formal monitoring, it is useful to further differentiate between light monitoring and rigorous monitoring: - Light monitoring aims to provide timely feedback on new activities (or new locations or target groups) or aspects of the project’s theory of change (activity-to-output or output-to-IR change) logic that staff are less confident about, to check for early signs that progress is being made and that assumptions are holding true while there is still ample time to make adjustments if necessary.3 - Rigorous monitoring aims to collect representative data for evidence-based project management, reporting and learning, not just at midterm but throughout project implementation.

Adaptive environmental assessment and management: a new approach to environmental impact assessment - Jones, Michael L.; Greig, Lorne A. (New directions in environmental impact assessment in Canada, 1985)

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

5 Principles to Guide Adaptive Leadership - Ramalingam, Ben; Nabarro, David; Oqubuy, Arkebe; Carnall, Dame Ruth; Wild, Leni (Harvard Business Review, 2020)
How you respond to a crisis will have repercussions for years to come. The Covid-19 pandemic is constantly evolving, with leaders facing unpredictability, imperfect information, multiple unknowns, and the need to identify responses quickly — all while recognizing the multi-dimensional (health-related, economic, social, political, cultural) nature of the crisis. Responding to the crisis requires adaptive leadership, which involves what we refer to as the 4 A’s: Anticipation of likely future needs, trends and options. Articulation of these needs to build collective understanding and support for action. Adaptation so that there is continuous learning and the adjustment of responses as necessary. Accountability, including maximum transparency in decision-making processes and openness to challenges and feedback.
Keywords: Crisis management; Leadership

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.

Program Cycle - Discussion Note: Adaptive Management - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

What is adaptive management? - Wilson, Gregory (ΔNTYLLES, 2016)
Recently there has been growing recognition that most development challenges are in actual fact ‘wicked’ problem that requires development actors to recognize that the optimal management approaches…

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .

Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments―now updated with new techniques for larger projectsToday, the pace of project management moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromising value, quality, or business discipline. In Agile Project Management, Second Edition, renowned agile pioneer Jim Highsmith thoroughly updates his classic guide to APM, extending and refining it to support even the largest projects and organizations.  Writing for project leaders, managers, and executives at all levels, Highsmith integrates the best project management, product management, and software development practices into an overall framework designed to support unprecedented speed and mobility. The many topics added in this new edition include incorporating agile values, scaling agile projects, release planning, portfolio governance, and enhancing organizational agility. Project and business leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, quality, and constraints. This edition’s coverage includes: Understanding the agile revolution’s impact on product development Recognizing when agile methods will work in project management, and when they won’t Setting realistic business objectives for Agile Project Management Promoting agile values and principles across the organizationUtilizing a proven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five stages of the agile project: Envision, Speculate, Explore, Adapt, and CloseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for executives and management  The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader

Monitoring and learning for country-level portfolio decision-making and adaptation - Buffardi, Anne L; Mason, Paige; Hutchings, Claire; Sharp, Samuel (Briefing Note, 2019)
Most measurement and adaptive management approaches were developed for and from individual projects. This briefing aims to guide measurement and management of country-level portfolios of work. It identifies potential purposes portfolio-level analyses can fulfil, types of adaptation, and the relative role of monitoring, learning and evaluation (MEL). Drawing on reviews of practice from the United States Agency for International Development (USAID) and the United Kingdom Department for International Development (DFID), guidance notes, and experiences of members of the Global Learning for Adaptive Management (GLAM) initiative, it offers recommendations and considerations that are particularly relevant for this level of analysis and management. Key messages - Portfolio-level analyses can serve eight potential purposes, each of which answers different questions, involves adaptation at different times and levels, and requires different types of evidence. Identifying the purpose(s) and how the component parts relate to each other should guide the development of monitoring and learning systems. - Portfolios are oriented more towards breadth than depth, involve more people with different perspectives, and draw on multiple sources of evidence with potentially greater variation in quality. - In practice, four activities appear to be applied most frequently at a portfolio level: alignment of indicators and aggregation of monitoring data; synthesis of multiple sources and types of information to provide a summary of outputs, outcomes, common observations and trends; periodic review and reflection sessions; and strategic planning, design or refresh of the portfolio strategy. - The extent to which evidence-informed portfolio management is facilitating learning and adaptation has not been well documented to date, and we suggest potential indicators to do so.

Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (Briefing Paper, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

LearnAdapt: a synthesis of our work on adaptive programming with DFID/FCDO (2017–2020) - Laws, Ed; Pett, Jamie; Proud, Emma; Rocha Menocal, Alina (Briefing Note, 2021)
Key takeaways. • Development is not linear or straightforward, but rather complex, uncertain and context-specific. This calls for international development actors to work differently, in ways that are based on deliberate experimentation, learning and adaptation, to inform decisions and drive effective development. • Although it might go by different names, adaptive programming has been used in a variety of areas and fields in both the public and private sectors. Development practitioners have much to learn from and contribute to these different approaches and experiences. • Trust and relationship-building across all relevant stakeholders are among the most critical enabling factors for adaptive management. They are essential to give partners the space, autonomy and authority needed to try, test, reflect, iterate and feed back at the frontline of implementation, and to give donors the confidence that decisions are being made on the basis of evidence and learning to improve effectiveness. • There is an urgent need to rethink how accountability requirements, results frameworks, value for money considerations, performance markers, procurement and contracting mechanisms and other processes are understood and applied so that they are better aligned with and can support adaptive management more effectively. • The role of senior managers leading adaptive programmes from the donor side should be to create a space for experimentation and learning. Funders should hold their partners accountable for learning and how it feeds into effective programming, rather than for delivering on predetermined targets. • While formal guidance is important, leadership, champions, institutional incentives, a supportive management culture and appropriate mindsets are essential to encourage adaptive ways of working. • Adaptive management is resource-intensive. It requires skill, commitment, time for building trust and investments in learning. It is a journey, not an immediate destination – so it calls for patience, open-mindedness and a more nuanced approach to risk.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Prospects practice paper, 2, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptiveness through ‘simplest tools and practices’ - Prieto Martin, Pedro (Institute of Development Studies, 2017)
In recent years, more and more influential development organisations have been openly recognising the central role that adaptive management capacities – the ability to keep improving strategies and actions as programmes unfold – play for the success of complex interventions. As a result, there has been a rich exchange of ideas and experiences on how to promote adaptiveness in development. But development organisations and professionals are having a hard time translating the many adaptive theories and recommendations into improved practices and outcomes. They are generally failing to adjust the design and operation of programmes to accommodate incipient lessons learnt and the unexpected changes in the context. Nowadays, most programme adaptations still take the form of a change of direction once it is clear that things have gone really wrong. Why is so difficult to put what we know about adaptiveness into practice? And more importantly: what can be done to improve this situation?

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. --- You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Adaptive leadership in the coronavirus response - Ramalingam, Ben; Wild, Leni; Ferrari, Matt (ODI, 2020)
The coronavirus pandemic poses unprecedented challenges to science, policy and the interface between the two. How – and how quickly – policy-makers, practitioners and researchers react to this emerging and complex crisis is making a profound difference to people’s lives and livelihoods (WHO, 2020). But how can we ensure effective collective decision-making on the basis of emerging evidence, changing trends and shifting scientific understanding, all in the face of considerable uncertainty? Recent experience highlights the need for adaptive leadership in national and global responses to the outbreak. This briefing paper sets out key principles for what this might look like, and proposes a roadmap for policy-makers, practitioners and researchers to move towards such an approach as they tackle the unfolding crisis. Key messages Tackling the coronavirus outbreak requires adaptation at operational and leadership levels. Operationally, there is scope to strengthen evidence-based adaptive management practices, to adjust the mix and type of interventions being implemented and learn as we go so as to achieve shared goals. This requires adaptive leadership capacities, being open and transparent about learning, using collective decision-making processes and building trust with communities and individuals.

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Politically Agile Programming, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

Try, learn, adapt, repeat: T/A Learn reflections - Alan (www.globalintegrity.org, 2015)
By Alan Hudson — November 16, 2015. I spent last week in Rio de Janeiro (tough assignment, I know), participating in the Transparency and Accountability Initiative’s third T/A Learn Annual Workshop. As the report of the second Annual Workshop, held...

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must transition to new perspec-tives that account for the complex adaptive needs of organizations. In this paper, we propose that leadership (as opposed to leaders) can be seen as a complex dynamic process that emerges in the interactive "spaces between" people and ideas. That is, leadership is a dynamic that transcends the capabilities of individuals alone; it is the product of interaction, tension, and exchange rules governing changes in per-ceptions and understanding. We label this a dynamic of adaptive leadership, and we show how this dynamic provides important insights about the nature of leadership and its outcomes in organizational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors involved in producing it, and we present a set of innovative methods for capturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organizational behavior and organization and management theory.

Navigating adaptive approaches for development programmes - Pett, Jamie (Working Paper, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice

Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

The Strategy Testing Workbook: Politically-Smart Adaptive Programming in Complex Environments - Nixon, Nicola; O'Donnell, Carolyn; Rajalingam, Gobie; Tweedie, Pauline; Sullivan, Elizabeth (The Asia Foundation, 2024)
The guide begins with a section on what we at TAF have learned about practicing Strategy Testing, highlighting things that we didn’t know when we started out. Some of these lessons may seem obvious, but others may strike you as less so. In any case, we believe that, when taken together, they provide a useful reminder of some of the pitfalls that arise in efforts to practice Adaptive Management. Moreover, they help to remind us that there are multiple layers to doing Strategy Testing effectively as a system instead of reducing it to its component parts and applying them mechanistically. Thus these lessons are useful to read now and to revisit later. The guide then comprises three more sections: • Part 1, the Design Stage, involves constructing the system and making sure everyone is on board; • Part 2, the Inception Phase (start-up phase), helps the implementing team to make the leap from the ideal initially set out in the design stage to the grounding, support, and frameworks that the team will need to implement Strategy Testing in a meaningful and impactful way. We’ve found that the gap between design and implementation is very often the cause of an ineffective ‘all talk and no walk’ approach to Adaptive Management. And finally; • Part 3 covers Program Implementation – the practices, knowledge, and culture needed for the feedback loop that underpins Strategy Testing. The guide can be used for individual or group learning, or it can be used directly to inform Reflection Sessions (see Section 3) through the questions we raise or the activities herein.

Adaptive Management - Jenal, Marcus; Cunningham, Shawn (Annual Reflection 2019, 2019)

Delivering institutional reform at scale: Problem-driven approaches supported by adaptive programming - Manuel, Clare (Synthesis Paper, 2, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). Second synthesis paper - Delivering institutional reform at scale: problem-driven approaches supported by adaptive programming February 2016 Drawing on our experience on the ground, this peer-reviewed paper suggests how problem driven approaches, supported by adaptive programme management can be implemented at scale in relation to donor programming aimed at institutional reform and improving state capability.
Keywords: IMPORTANT

Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncertainty in the management of such renewable resources as fish and wildlife. He argues that scientific understanding will come from the experience of management as an ongoing, adaptive, and experimental process, rather than through basic research or the development of ecological theory. The opening chapters review approaches to formulating management objectives as well as models for understanding how policy choices affect the attainment of these objectives. Subsequent chapters present various statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harvest policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and conflicting objectives as well as biophysical factors. Throughout the text dynamic models and Bayesian statistical theory are used as tools for understanding the behavior of managed systems. These tools are illustrated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and resource managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of policy design.

Adaptive management: why we find it so hard to operationalise - Teskey, Graham (Abt Associates - Governance Soapbox, 2018)

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (White Paper #1104, 2011)

Bridging Real-Time Data and Adaptive Management in International Devepment - Case Study Report - Ramalingam, Ben; Barnett, Inka; Valters, Craig; Oppenheimer, Carrie; Levy, Anna; Hernandez, Kevin (IDS, 2017)

A top Toolkit on Adaptive Management. But is that a good idea? – FP2P - Green, Duncan (From Poverty to Power, 2021)

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

Adaptive management: an overview of the concept and its practical application in the Scottish context - Blackstock, Kirsty; Brown, Katrina; Gimona, Alessandro; Prager, Katrin; Irvine, Justin (The James Hutton Institute, 2016)

How to do Adaptive Management in 15 easy steps – from a top new toolkit – FP2P - Green, Duncan (From Poverty to Power, 2021)

Adaptive Management: Responding to the evolving needs of PRIME's complex systems - Picon, Diana; Wild, Lorenz (Mercy Corps, 2015)

The road to adaptive management: knowledge, leadership, culture and rules - Byrne, Karri Goeldner; Sparkman, Timothy; Fowler, Ben (The BEAM Exchange, 2016)
Keywords: IMPORTANT; Practice

Developing an effective adaptive monitoring network to support integrated coastal management in a multiuser nature reserve - Vugteveen, Pim; van Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support Integrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling actions essential to accomplish and sustain monitoring excellence to support ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online data portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioeconomic data and links research-driven and policy-driven monitoring for system analysis using indicators of pressures, state, benefits, and responses. The approach and concepts we elaborated are transferable to other coastal regions to accomplish ICM in complex social-ecological systems in which scientists, multisectoral stakeholders, resource managers, and governmental representatives seek to balance long-term ecological, economic, and social objectives within natural limits.
Keywords: IMPORTANT

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Second (and Third) Thoughts on Adaptive Management and Thinking and Working Politically - Green, Duncan (From Poverty to Power, 2022)
Self-Critical reflections on AM and TWP. Linking it with The Hype Cycle - "it feels like we are heading downward to the ‘trough of disillusionment’ form the initial peak of ‘inflated expectations’, but we will bounce back to something more sustained, that becomes a permanent feature of the aid landscape".

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

When Complex is as Simple as it Gets: Guide for Recasting Policy and Management in the Anthropocene - Roe, Emery (IDS Working Paper, 2023)
Many readers recognise and understand that complex is about as simple as it gets for major policy and management. This guide is for those unwilling in the Anthropocene to shrink back into the older platitudes about ‘keep it simple’ and ‘not to worry, we’ll scale up the analysis later on’. This guide offers key concepts, methods, counternarratives, and analogies that recast major policy and management issues in ways that do not deny their complexity but help render them more tractable for action.

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Adaptive management: What it means for CSOs - O’Donnell, Michael (Bond, 2016)
Keywords: IMPORTANT

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

Adaptive Learning Guide: A pathway to stronger collaboration, learning, and adapting - Ross, Joey; Karlage, James; Etheridge, James; Alade, Mayowa; Fifield, Jocelyn; Goodwin, Christian; Semrau, Katherine; Hirschhorn, Lisa (USAID MOMENTUM Knowledge Accelerator, 2021)
The purpose of this Adaptive Learning Guide is to provide MOMENTUM project teams with the information and resources to integrate adaptive learning into the design, implementation, and improvement of MNCH/FP/RH programs. This guide provides a conceptual introduction to adaptive learning using links to existing resources and real-world examples of how adaptive learning can drive continuous learning and improvement in project work. The guide is built upon three foundational assumptions: We work in dynamic, often unpredictable environments. Unexpected turns of events will occur. Progress is rarely, if ever, linear. Integrating the principles and practices of USAID’s Collaborating, Learning, and Adapting Toolkit into projects and initiatives requires designing for learning and adaptation. We intend the guide to serve as a “starting point” for interested individuals and teams to begin or strengthen the processes that support the integration of adaptive learning into project work.

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2017 update) - Learning Lab (USAID, 2017)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Thoughts on the use of hypotheses in adaptive management - Sparkman, Timothy (BEAM Exchange, 2015)
New insights, opinions and perspectives on market systems development, from experts and practitioners.

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Managing staff transistions through CLA: preserving institutional memory as staff come and go - USAID (CLA Toolkit, 2019)
This document is relevant for any position or hiring mechanism. While this document does not explicitly address what happens when someone arrives into a newly-created position, which has its own set of challenges, many of the principles, actions, and resources can be applied in that context. Section 1 offers guidance for how to set up and implement systems at Mission/OU or office to ensure that all staff help preserve institutional memory and enable continuity of relationships. This section is for any staff in a Mission/OU working to build systems that improve handovers and knowledge capture and sharing across the Mission or OU. If a Mission or OU is just beginning to develop a system to manage staff transitions, you may want to start by developing a system within an office or team and then expand it out to other offices or to the Mission/OU writ large. Section 2 includes key principles and actions individuals could consider following when arriving or departing a position, regardless of hiring mechanism and position. This includes staff new to the Mission/OU and staff who are currently in the Mission/OU and are moving into a new position. Section 3 provides a select number of resources to help you take a systematic and comprehensive approach to manage staff transitions as effectively and efficiently as possible at the individual or organizational level.

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

Six things that help grant-makers learn and adapt - Murray, Aoife (Itad, 2017)
There’s an emerging body of literature identifying key strategies that can both improve learning and enable adaptive management amongst grant-makers. We recently reviewed a host of publications from eight grant-making organisations. Those organisations have diverse aims and approaches but we’ve identified six common themes that stand out: Strong leadership and facilitation enables successful learning and …

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

How adaptive M&E from the peace sector can help demonstrate the value of aid - Kratzer, Sebastian (2023)
Over the last decade, the peace sector has been developing and adapting Monitoring and Evaluation (M&E) systems and tools to fit their contexts and ways of working. This evolution may hold some insights for the aid community in how to go beyond more traditional, backwards-looking M&E to navigate today’s volatile, interest-based world of politics and aid.

Measuring and Monitoring Adaptive Learning: A Landscape Review - LaFond, Anne; Adrian, Haley (USAID MOMENTUM Knowledge Accelerator, 2022)
This landscape review on measuring and monitoring adaptive learning highlights the learning from five adaptive programming guidelines and toolkits and one implementation science framework to inform the monitoring and evaluation of adaptive learning. The introduction of adaptive learning processes and skillsets in global health programming is part of an emerging strategy to advance a learning culture within projects and teams to improve health program performance. The monitoring and evaluation of adaptive learning is an emergent field aiming to monitor how adaptive learning processes have been introduced, how they are used, and whether they are having the intended results. Although there is a growing body of literature on adaptive programming more generally, there is a limited knowledge base on the monitoring and evaluation of adaptive learning interventions and their impacts. Unlike other implementation strategies or program management approaches, there are no standard metrics or a monitoring and evaluation framework to track the integration, implementation, and effectiveness of adaptive learning in health programming.

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Rapport 2016:07, 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

“Everyone is talking about it, but no one is doing it”: How implementation research is – or isn’t – informing adaptation towards scale in international education - Dowd, Amy Jo (International Journal of Educational Development, 2024)
With growing evidence of what works in education, governments and their partners strive towards scale. While implementation research to adapt solutions holds promise for testing what works, where and for whom, its use in education is limited. Sixty-three international education stakeholders from government, academia, think tanks, local and international non-governmental organizations, multi- and bi-laterals and foundations offer insight into three modes of implementation research that differ on responsiveness, timeliness and stakeholder collaboration. They speak to the primacy of government involvement, trust and curiosity in collaborative efforts. This study explores enabling factors for evidence-based implementation improvement on the pathway to scale.
Keywords: Evidence-based practice; Implementation research; International education

Evidence base for Collaborating, Learning, and Adapting: summary of the literature review (2020 update) - Learning Lab (USAID, 2020)
The LEARN contract and the United States Agency for International Development/Bureau of Policy, Planning, and Learning (USAID/PPL) are managing an area of work known as the Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer the following key learning questions: ● Does an intentional, systematic, and resourced approach to collaborating, learning, and adapting (CLA) contribute to organizational effectiveness and/or development outcomes? ● If so, how? And under what conditions? ● How do we know? How do we measure any contribution that CLA makes to development results? As we began this work, we identified the need to conduct a literature review looking at these questions to understand what is known, what remains unknown, and how others have tried to answer these questions to date. We were primarily interested in answering these questions: ● What evidence is there, if any, that collaborating, learning, and/or adapting contributes to organizational effectiveness, development outcomes, or both? What are the strongest pieces of evidence? ● Does the literature identify any factors critical to CLA that are not currently included in the CLA framework? ● Who else is working on measuring the impact of collaborating, learning and adapting? ● What methods and measures did researchers use to study the effects of collaborating, learning, and adapting? ● Where are there gaps in the research relevant to collaborating, learning, and adapting? ● When taken together, what practical guidance does the evidence for collaborating, learning, and adapting offer to practitioners and policy makers to improve organizational effectiveness and development outcomes?

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

Interview protocol: Most significant turning points - Prieto Martin, Pedro; Faith, Becky (Institute of Development Studies, 2017)
This interview protocol was used for a research project on adaptiveness in technology for governance initiatives in Kenya. For more information, please read the research report at: Prieto Martin, P.; Hernandez, K.; Faith, B. and Ramalingam, B. (2017) Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya, MAVC Research Report, Brighton: Institute of Development Studies, ids.ac.uk/project/making-all-voices-count
Keywords: IMPORTANT

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Transforming M&E for Uncertain and Complex Contexts: The UNDP’s Innovation Sandbox Approach - Fraser, Dugan; Haldrup, Søren (Powered by Evidence Podcast, 2022)
How can we transform monitoring and evaluation (M&E) into a more adaptive, emergent process to address uncertainty and complexity in todays’ world? How do we move from compliance and accountability to learning – to support better, more timely, decisions? Join GEI Program Manager, Dugan Fraser, as he discusses these questions and others with Special Guest, Søren Haldrup, from UNDP's Strategic Innovation Unit where he manages UNDP's innovation facility and leads a new initiative called the M&E Sandbox.

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Responding to change: Learning to adapt in development cooperation - Engel, Paul; Keijzer, Niels; Ørnemark, Charlotte (Policy Management Brief 19, 2007)

Systems-aware social accountability: Harnessing Practitioner Insights for More Responsive Governance - Guerzovich, Florencia (Pact, 2023)
The framework’s four principles, described below, are not exclusive to social accountability interventions; for example, Pact has published tools on how to use political economy analysis or integrate adaptive management principles into programming. Rather, the principles highlight how – by including the right combination of mindsets, management approaches, analytic approaches and tools – practitioners can develop and apply a deep understanding of a system to improve relationships within it, in support of greater accountability and improved service delivery. - Use a Holistic Lens - Recognize that there is always a system; understand and engage with it​: Developing a strong understanding of the system in which a project works and effectively integrating this knowledge into implementation increases the chances that local actors will sustain the interventions. - Right Fit the Approach​ - Equipped with a holistic understanding of the context, teams identify where they have a comparative advantage in a specific system. In other words, they identify where their resources, expertise and partners have the greatest potential for impact, then set realistic targets that they revise periodically. -Orchestrate Across The System -​ Practitioners take a networked, rather than a top-down, approach to capitalize on their convening power and maximize opportunity to facilitate the most-promising alignments across and within their projects, portfolios and systems. Orchestrators use their individual power, relationships and insight into the local system to enable, not impose, promising interactions and mitigate the risks of damaging ones. - Manage Adaptively - Monitor, evaluate and reflect on emerging patterns of data, evidence and learning to inform decision-making within and, equally importantly, across project cycles. Where possible, practitioners should consider how to use short-term projects to play a long-term game by linking new projects to the lessons and results of their predecessors and ensuring that they are responsive to the evolving context, particularly opportunities, limits and risks.

Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (CID Faculty Working Paper, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Technical assistance: a practical account of the challenges in design and implementation - Nastase, Alexandra; Rajan, Alok; French, Ben; Bhattacharya, Debarshi (Gates Open Research, 2021)
Technical assistance is provided to country governments as part of international development programmes to support policymaking or strengthen state capability. This article presents the conceptual evolution of ‘technical assistance’ linked to capacity development, starting with programmes aiming exclusively to enhance individual capacity in the 1950s to 1970s and progressing to complex systems approaches in the past ten years. It also presents some of the frequent challenges in designing and implementing technical assistance, drawing from the existing literature and the authors’ experience in international development. The article summarises the latest thinking about delivering more effective development, including the adaptive management practices and the initiatives to strengthen evidence about what works. Finally, we complement this article with a follow-up open letter reflecting on the current policy options and opportunities for change.

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives--rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations--they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making, Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (Health Communication Innovation Webinar, 2016)

‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (GPSA Note 12, 2016)
Keywords: IMPORTANT

Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

What have we learned about learning? Unpacking the relationship between knowledge and organisational change in development agencies - Yanguas, Pablo (German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Development cooperation has spent decades wrangling over the merits, evidence, and implications of what we may term “the learning hypothesis”: the idea that increased knowledge by development organisations must logically lead to increased effectiveness in the performance of their development activities. Organisations of all stripes have built research and monitoring and evaluation (M&E) departments, adopted a multitude of knowledge management systems and tools, and tinkered with different ways to structure their organograms to stimulate knowledge sharing and learning. The topic of organisational learning is particularly significant as the global development community grapples with increasingly complex problems and the aspiration of evidence-based policymaking. This paper presents an analytical framework for interrogating “the learning hypothesis”, breaking it down into causal steps: knowledge causes learning, learning causes organisational change, change causes effectiveness. The framework focuses on the first two sub-hypotheses, mapping out the conceptual space around them by outlining potential relationships between different types of knowledge – tacit and explicit, internal and external – and between different types of learning – operational and strategic. This map provides a foundation for three key research questions: What impact has the rising knowledge agenda had on development organisations? Which factors appear to enable or inhibit organisational learning? What is the relationship between operational and strategic learning and organisational change? A review of available evaluations and studies, including two cases from former UK Department for International Development (DFID) and the World Bank, reveals that there is insufficient evidence to support the causal claim that knowledge leads to learning and thereby to organisational change in development agencies. Sources point to tacit learning prevailing while explicit knowledge management systems flounder, and external advocacy agendas appear more compelling than internal research and evaluation products. It is not entirely clear how, or indeed, whether operational and strategic learning intersect, with delivery-level lessons hardly aggregating into structural or policy shifts. Organisational change – even that aimed at enhancing learning – is rarely based on lessons learned from practice. More research is necessary to fully unpack the learning hypothesis, but what limited evidence is available disproves rather than confirms its central claim. This has significant implications for the future of learning in development agencies as advocated by thought leaders, researchers, and reformers. In particular, the latter should consider an evidence-based reassessment of the function and value-for-money of research and M&E in development practice, and a more critical examination of the politics of external advocacy efforts around innovative aid approaches like thinking and working politically, adaptive management, or results-based management.

Paradoxes and partnerships: a study of knowledge exploration and exploitation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships balance knowledge exploration and exploitation in contexts that are rife with paradoxes. It draws on paradox theory to examine the partnership’s response to the explore-exploit relationship.

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

Leading Change Through Adaptive Design - Berstein, Maya; Linsky, Marty (Stanford Social Innovation Review, 2016)
By integrating two practices—design thinking and adaptive leadership—social innovators can manage projects in a way that’s both creatively confident and relentlessly realistic.

Glossary of Key Terms in Evaluation and Results Based Management - OECD (OECD, 2009)

Local Systems Position Paper - USAID (USAID, 2024)
The Local Systems Position Paper describes the key approaches USAID will use to translate systems thinking into systems practice. It focuses on ways USAID can better understand and engage local systems to support them in producing more sustainable results. Systems thinking is a mindset and set of tools that we use to understand how systems behave and produce certain results or outcomes. Systems practice is the application of systems thinking to better understand challenges and strengthen the capacity of local systems to unlock locally led, sustained progress. The shift from systems thinking to systems practice is driven by a desire to integrate systems practice throughout the Program Cycle and increase our capacity to actively and adaptively manage programming in ways that recognize complexity and help make our programs more effective and sustainable. These approaches will be utilized alongside and within the context of USAID’s policies and guidance, including technical guidance for specific sectors, as well as evidence and lessons learned from partners around the world. Systems thinking is a long-standing discipline that can serve as a powerful tool for understanding and working with local systems. It has been a consistent component of USAID’s decades-long commitment to locally led development and humanitarian assistance. USAID uses systems thinking to better understand the complex and interrelated challenges we confront – from climate change to migration to governance – and the perspectives of diverse stakeholders on these issues. When we understand challenges as complex systems – where outcomes emerge from the interactions and relationships between actors and elements in that system – we can leverage and help strengthen the local capacities and relationships that will ultimately drive sustainable progress. Recognizing this, in 2014, USAID released the Local Systems Framework, outlining ten principles to help USAID staff, partners, and local stakeholders place local systems at the center of all of our efforts to promote sustainability. Since then, development and humanitarian actors have embraced systems thinking as a concept and reiterated its importance in other policies, strategies, and tools, across sectors and regions. When USAID released its Localization Vision and Approach in 2022, it included local systems practice as a core component of adapting policies and program practices. Building on the success of the Local Systems Framework, this position paper reiterates USAID’s commitment to systems practice and presents six approaches that will help USAID strengthen and further embed systems practice in all of our work

Principles for managing in complexity - Proud, Emma (LearnAdapt, 2020)
Written by Toby Lowe and Shaheen Warren (Centre for Public Impact) and Sam Sharp (Overseas Development Institute), with input from Jamie…

Donor perceptions and processes: Risks to success of adaptive programming? - Browse - Knowledge Platform Security & Rule of Law - Donovan, Elbereth (Knowledge Platform - Security & Rule of Law, 2017)
Keywords: IMPORTANT

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

Review of Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Uphoff, Norman (Economic Geography, 1985)

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Learning, monitoring and evaluating: achieving and measuring change in adaptive programmes - Callaghan, Sarah; Plank, Georgia (Synthesis Paper, 5, 2017)

Adaptive programming - Vowles, Pete (DFID Bloggers, 2013)
Staff blogs from the UK Department for International Development. Get real-life perspectives from those on the ground to fight poverty and join in the debate.

Lessons for PFM Reform - the PDIA Approach in Africa - Bento, Joana (Public Financial Management Blog - IMF, 2021)
Some important lessons are as follows: First, identifying a policy problem is critical for reforms to get traction both at a political and administrative level. Second, appropriate solutions can emerge from a process of experimentation, iteration, and adaptation. Third, building teams and institutional capabilities is a critical part of solving complex problems in a sustainable way.

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

Managing complexity (and chaos) in times of crisis. A field guide for decision makers inspired by the Cynefin framework - Snowden, Dave; Rancati, Alessandro (Publications Office of the European Union, 2021)
This field guide helps to navigate crises using the Cynefin framework as a compass. It proposes a four-stage approach through which we can: - assess the type of crisis and initiate a response; - adapt to the new pace and start building sensing networks to inform decisions; - repurpose existing structures and working methods to generate radical innovation; - transcend the crisis, formalise lessons learnt and increase resilience. The guide stresses the importance of setting and managing boundaries, building informal structures, keeping options open, distributing engagement and keeping an ongoing assessment of the evolving landscape. Action items, real life examples and demonstrations complement the references to the developing theoretical framework.

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)

Re-Perceiving Results: Aid Programs and Change in Fragile Societies - van Veen, Erwin; Rijper, Alies (Policy Brief, 2017)
Aid programmes need to be able to adapt their objectives and operations to changes in their political environment, since development processes are subject to political contestation. Change takes time and is often a matter of seizing the opportunity.
Keywords: IMPORTANT

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Publishing, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Exploring ways to reconcile accountability and learning in the evaluation of niche experiments - Regeer, Barbara J.; de Wildt-Liesveld, Renée; van Mierlo, Barbara; Bunders, Joske F. G. (Evaluation, 2016)
While evaluation is seen as a mechanism for both accountability and learning, it is not self-evident that the evaluation of niche experiments focuses on both accountability and learning at the same time. Tensions exist between the accountability-oriented needs of funders and the learning needs of managers of niche experiments. This article explores the differences in needs and expectations of funders and managers in terms of upwards, downwards and internal accountability. The article shows that as the multi-stakeholder contexts in which niche experiments take place give rise to various requirements, tensions in evaluation are essentially a specific manifestation of tensions between niche experiments and their multiple contexts. Based on our findings, an adjusted accountability framework is proposed, including several strategies that can reconcile a learning approach with accountability needs in niche experiments aiming to change current practices in a more sustainable direction.

Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Rondinelli, Dennis A. (Methuen, 1983)
International assistance programmes for developing countries are in urgent need of revision. Continuous testing and verification is required if development activity is to cope effectively with the uncertainty and complexity of the development process. This examines the alternatives and offers an approach which focuses on strategic planning, administrative procedures that facilitate innovation, responsiveness and experimentation, and on decision-making processes that join learning with action. A useful text for academics and practitioners in development studies, geography and sociology.

Building capability by delivering results: Putting Problem-Driven Iterative Adaptation (PDIA) principles into practice - Andrews, Matt; Pritchett, Lant; Samji, Salimah; Woolcock, Michael (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Working between systems and complexity - a practitioners guide - Allen, Will (learningforsustainability.net, 2025)
How practitioners navigate between systems and complexity thinking. Exploring structure and emergence in real-world collaboration and adaptive work.

Transformation, politics and implementation: smart implementation in governance programs - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos, 2017)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps? Through theoretical considerations and nine case studies, the GIZ traces implementation processes and identifies underlying guiding principles which provide the flexibility and adaptability that is necessary for acting in complex contexts. Main findings show that an adaptive and reflexive management structure is crucial for successful implementation. Quick iteration and tight feedback loops facilitate adaptation and reorientation. Contextsensitive knowledge and constant monitoring create a space for learning and innovation. A joint vision for the future which is used for orientation purposes and can be modified according to new findings and developments fosters fruitful cooperation.

DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best possible performance across a large and multifaceted aid programme is, however, a complex management challenge. This report reviews ICAI’s previous 44 reports and looks at how well DFID ensures positive, long-term, transformative impact across its work.

A New Policy Narrative for Pastoralism? Pastoralists as Reliability Professionals and Pastoralist Systems as Infrastructure - Roe, Emery (ESRC STEPS Centre, 2020)
This paper proposes that pastoralist systems are better treated, in aggregate, as a global critical infrastructure. The policy and management implications that follow are significant and differ importantly from current pastoralist policies and recommendations. A multi-typology framework is presented, identifying the conditions under which pastoralists can be considered real-time reliability professionals in systems with mandates preventing or otherwise avoiding key events from happening. The framework leads to a different policy-relevant counternarrative to pastoralism as understood today. Some features of the counternarrative are already known or have been researched. The paper’s aim is to provoke further work (including case research and interactions with decisionmakers) on how robust the counternarrative is as a policy narrative for recasting today’s pastoralist policy and management interventions.

Strengthen Your Team’s CLA Practices: Introducing the CLA Maturity Tool for USAID Implementers - Social Impact , Inc (2023)
The Collaborating, Learning & Adapting (CLA) Maturity Tool has been used by USAID operating units since 2015. The tool enables staff to self-assess their current CLA practice and plan ways to improve their internal and external collaboration, organizational learning efforts, and adaptive management practices. Recently, SI built on this resource to create the CLA Maturity Tool for implementing partners (IPs) to provide a version that speaks more directly to the experience of international and local organizations. Learn more here.

Announcement of CLA Learning Network Launch - Lab, Learning (USAID Learning Lab, 2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localworks program, is pleased to announce the launch of a Learning Network focused on building the evidence base for Collaborating, Learning and Adapting (CLA).

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Keywords: Reference / Research; Research

Lessons for Effective resilience programs: a case study of the RAIN program in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and flexible funding as key program design features if progress in resilience building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respond effectively to changing circumstances in order to better meet the needs of communities and to create the necessary conditions for relief-to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensure that development gains achieved during one program period are directly leveraged by subsequent programs, thereby increasing the effectiveness of resilience programs.

What difference does CLA make to development? Key findings from a recent literature review (2020 update) - Learning Lab (USAID, 2020)
USAID’s Bureau for Policy, Planning and Learning and its LEARN support contract are working to integrate systematic, intentional and resourced collaborating, learning and adapting (CLA) throughout program planning and implementation to achieve more effective development programs. As part of this effort, USAID is exploring several approaches to understand whether and how strategic collaboration, continuous learning and adaptive management make a difference to organizational effectiveness and development outcomes. To begin this work, we have undertaken a foundational literature review of academic and gray literature to answer our key learning questions: • Does an intentional, systematic and resourced approach to collaborating, learning and adapting contribute to organizational effectiveness? To development outcomes? • If so, how? And under what circumstances? • How do we measure the contribution? The 13 key findings, mapped to the CLA Framework below, are described in greater detail in the following pages.

Harnessing Complexity: Organizational Implications of a Scientific Frontier - Axelrod, Robert M.; Cohen, Michael D. (Free Press, 1999)
Recent advances in the study of complexity have given scientists profound new insights into how natural innovation occurs and how its power can be exploited. Now two pioneers in the field, Robert Axelrod and Michael D. Cohen, provide leaders in business and government with a guide to complexity that will help them make effective decisions in a world of rapid change. Building on evolutionary biology, computer science, and social design, Axelrod and Cohen have constructed a unique framework for improving the way people work together. Their approach to management is based on the concept of the Complex Adaptive System, which can describe everything from rain forests to the human gene pool, and from automated software agents to multinational companies. The authors' framework reveals three qualities that all kinds of managers must cultivate in their organization: "Variation" What is the best way to manage the development of software? Should the problem be broken up into small pieces for programmers working independently, thus enhancing variation, or should there be a centralized hierarchy of programmers ruled by a chain of command? The authors show how the decentralized creation of variation combined with the centralized maintenance of standards was the key to the success of the Linux "open source software" project, which brought together thousands of volunteers in cyberspace to produce an operating system that can outperform Microsoft's. "Interaction" Why did northern Italy prosper while southern Italy remained poor? Recognizing the internal interactions of a Complex Adaptive System -- be it a national region, a company, or a nonprofit group -- reveals vitalnetworks of trust. Axelrod and Cohen explain that in successful adaptive systems, rich networks of horizontal linkages foster cooperation and provide an advantage over other less cooperatively networked groups. In the case of Italy, voluntary associations created networks of trust in the Middle Ages that became northern Italy's critical advantage over the south. "Selection" Is a Pulitzer Prize better than a National Book Award? How can foundations and corporations design competitions that have a positive effect on the evolution of excellence? The authors' framework makes clear that the worst selection processes are mired in orthodox standards that have not adapted to a new environment. The best selection processes, on the other hand, are created and run by leaders who understand how the standards they use can transform their organization and its environment. This simple, paradigm-shifting analysis of how people work together will transform the way we think about getting things done in a group. "Harnessing Complexity" is the essential guide to creating wealth, power, and knowledge in the 21st century.
Keywords: Organizational Behavior

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Moving Targets, Widening Nets: monitoring incremental and adaptive change in an Empowerment and Accountability programme. The experience of the State Accountability and Voice Initiative in Nigeria - Derbyshire, Helen; Barr, Julian; Fraser, Steve; Mwamba, Wilf (DFID, 2016)
Keywords: IMPORTANT; Practice

Inclusive rigour for complexity - Chambers, Robert (Journal of Development Effectiveness, 2015)
Rigour can be reductionist or inclusive. To learn about and understand conditions of complexity, emergence, nonlinearity and unpredictability, the inclusive rigour of mixed methods has been a step in the right direction. From analysis of mixed methods and participatory approaches and methods, this article postulates canons for inclusive rigour for research and evaluation for complexity: eclectic methodological pluralism; improvisation and innovation; adaptive iteration; triangulation; plural perspectives; optimal ignorance and appropriate imprecision; and being open, alert and inquisitive. Inclusive rigour is inherent in participatory methods and approaches, visualisations, group-visual synergy, the democracy of the ground and participatory statistics. Transparent reflexivity, personal behaviour and attitudes, and good facilitation are fundamental. Fully inclusive rigour for complexity demands many personal, institutional and professional revolutions.
Keywords: Evaluation; Mixed methods; Participatory methodologies; Research; paradigm; rigour

Multi-project programmes functions, forms and implications for evaluation and learning - Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. • At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. • To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of interventions intended to improve fiscal management, reduce corruption or introduce efficient public sector service delivery in African countries.These reforms often have limited results, however. They lead to new laws that are not properly implemented, and new organizations that have poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and suggests ways to overcome these limits. In the first half of the book, Andrews argues that reforms fail to make governments better when they are introduced as signals to gain short-term support--from donors and others. Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by implementing agents. The result is a set of new forms that do not function properly. Andrews uses examples to prove this point, ranging from efforts to introduce fiscal rules in Argentina to reforms aimed at international accounting standard adoption in many African countries, and anti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on government effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of initiatives ranging from results based management to civil service modernization and internal control regime adoption in governments like Kenya, Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governance challenges in developing countries. Lessons from these experiences suggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and implement reforms.

Peer reviews - Guidance for facilitators and participants - Wadley, Ian (Mediation Practice Series, 2021)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

When Knowledge is Power: Three Models of Change in International Organizations - Haas, Ernst B. (University of California Press, 1991)
Do governments seeking to collaborate in such international organizations as the United Nations and the World Bank ever learn to improve the performance of those organizations? Can international organizations be improved by a deliberate institutional design that reflects lessons learned in peacekeeping, the protection of human rights, and environmentally sound economic development? In this incisive work, Ernst Haas examines these and other issues to delineate the conditions under which organizations change their methods for defining problems. Haas contends that international organizations change most effectively when they are able to redefine the causes underlying the problems to be addressed. He shows that such self-reflection is possible when the expert-generated knowledge about the problems can be made to mesh with the interests of hegemonic coalitions of member governments. But usually efforts to change organizations begin as adaptive practices that owe little to a systematic questioning of past behavior. Often organizations adapt and survive without fully satisfying most of their members, as has been the case with the United Nations since 1970. When Knowledge Is Power is a wide-ranging work that will elicit interest from political scientists, organization theorists, bureaucrats, and students of management and international administration.

Practicing what we preach — our experience rethinking M&E in complex settings - Bina, Andrea; Vester, Søren (UNDP Strategic Innovation, 2023)
The UNDP has been exploring new approaches to M&E to better understand and address complex systems challenges. Traditional linear project-based planning and evaluation methods are insufficient for dealing with the unpredictable nature of such systems. The UNDP’s new Strategic Plan calls for a shift in M&E practices to align with the complexity of today’s global challenges. Key points from the blog post include: Learning and Adapting: There’s a need for continuous learning and adaptation in M&E practices to effectively address complex problems like transitioning to a circular economy. Longer Time Horizons: Substantive change takes time, and it’s often unclear what the results will look like, making it difficult to track progress. Aggregate Impact: Evaluating interconnected interventions as a portfolio is crucial because they cannot be assessed in isolation. Contribution vs. Attribution: Focusing on the contribution to broader change processes is more important than attributing specific outcomes to individual actions. The UNDP has initiated the M&E Sandbox to experiment with and learn from innovative M&E practices. This collaborative space has attracted participants from over 180 organizations, highlighting a shared interest in evolving M&E to better understand change in contexts of uncertainty. A partnership with the Bill and Melinda Gates Foundation has also been formed to focus on M&E in food systems. The blog post emphasizes the importance of embracing uncertainty, experimenting, and collaborating to contribute to positive change in complex settings1.

Adaptive environmental assessment and management - Holling, C. S. (International series on applied systems analysis, 1978)
Keywords: Ecology; Economic development; Environmental impact analysis; Environmental protection

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Mediation Practice Series, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change

Diseño transformacional de proyectos - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Technically Strong and Politically Savvy: Enhancing Thinking and Working Politically when practicing the consevation standards at USAID - Schuttenberg, H.Z.; Stark, J.; Schueler, K. (USAID, 2026)
This supplemental guide offers practical advice for thinking and working politically (TWP) when practicing the Conservation Standards. The CS are a widely used, systematic approach for planning, monitoring, and adapting programs aiming to conserve biodiversity. TWP is an approach to international development that brings greater attunement to the political dynamics of the local programming context in order to enhance development results. Given strong evidence that political factors overwhelmingly drive the loss of biodiversity, this guide is based on the premise that conservation programs will be more effective when they skillfully integrate TWP.

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2014)
It is widely recognised that the foreign aid system - of which every country in the world is a part - is in need of drastic overhaul. There are conflicting opinions as to what should be done. Some call for dramatic increases to achieve longstanding promises. Others bang the drum for cutting it altogether, and suggest putting the fate of poor and vulnerable people in the hands of markets or business. A few argue that what is needed is creative, innovative transformation. The arguments in Aid on the Edge of Chaos are firmly in the third of these categories. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions that foreign aid is built on are more at home in early twentieth century industry than in the dynamic, complex world we face today. The reality is that economies and societies are less like machines and more like ecosystems. Aid on the Edge of Chaos explores how thinkers and practitioners in economics, business, and public policy have started to embrace new, ecologically literate approaches to thinking and acting, informed by the ideas of complex adaptive systems research. It showcases insights, experiences, and dramatic results of a growing network of practitioners, researchers, and policy makers who are applying a complexity-informed approach to aid challenges. From transforming approaches to child malnutrition, to rethinking process of macroeconomic growth, from rural Vietnam to urban Columbia, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. It argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.

Monitoring and evaluation for thinking and working politically - Aston, Thomas; Roche, Chris; Schaaf, Marta; Cant, Sue (Evaluation, 2022)
This article explores the challenges of monitoring and evaluating politically informed and adaptive programmes in the international development field. We assess the strengths and weaknesses of some specific evaluation methodologies which have been suggested as particularly appropriate for these kinds of programmes based on scholarly literature and the practical experience of the authors in using them. We suggest that those methods which assume generative causality are particularly well suited to the task. We also conclude that factoring in the politics of uncertainty and evidence generation and use is particularly important in order to recognize and value diverse experiential knowledge, integrate understandings of the local context, accommodate adaptation and realistically grapple with the power relations which are inherent in evaluation processes.

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Monitoring, Evaluation and Learning for Systems Change - McDonald, Lizzy; Simpson, Kate; Schramm, Carolin (Wasafiri, 2025)
Today’s critical challenges are complex and require system level change. Issues like ending poverty, reversing biodiversity collapse, creating more equitable and sustainable food systems, or ending health inequalities, will not respond to neat siloed technical interventions. These are not problems we can tackle head on. Rather, we need to change the conditions (systems) that create these problems. Consequently, many of the most ambitious philanthropic foundations are adopting ‘systems change’ approaches to their work. There is a critical need to better understand the impact of systems change interventions. This is for two reasons: 1) without being able to understand our impact we can’t learn about the efficacy of efforts and focus on doing more helpful action and less unhelpful action, and 2) without effective monitoring and evaluation it is hard to galvanise resources, whether as money, time, or enthusiasm. Traditional monitoring, evaluation and learning (MEL) approaches and practices struggle to respond to complexity. Many of today’s MEL approaches have been developed to serve funders keen to ‘prove’ the efficacy of their work and hold grantees accountable. This paradigm has produced approaches like ‘logical frameworks’ that seek to create a linear logic between intervention, outputs, outcomes and impact. Such approaches often pay scant regard to the activity (intentional or otherwise) of other actors in any system, and don’t adapt well to the characteristics of complex problems such as emergence, uncertainty, and interdependency. There is a fast-developing body of practice on MEL for systems change. A growing number of practitioners are experimenting with complexity informed approaches to MEL, and UNDP is pioneering an open-source set of tools and ideas.ii Wasafiri is contributing to this innovation by developing a MEL approach that builds on our (open access) Systemcraft Framework. iii Emerging approaches for systems change MEL are underpinned by some key principles. There is growing consensus on the need to be pragmatic and flexible, not just because it is a new field for many that requires a degree of mindset and behaviour change and different ways of working. MEL approaches for system change primarily focus on improving and learning and on identifying ways to adapt and pivot. This contrasts with linear approaches to implementation and measurement. Learning questions guide and co-exist alongside indicators to support continual learning and adaptation. These shifts will require a shift in relationships between funders and implementers from measuring and accountability to greater flexibility and patience, close engagement and learning together. There is pressure to show impact in less time. Reduced time horizons, increasing impatience and integration of new sets of agendas in development programming present challenges in the context of systems change. In an increasingly resource constrained context and amid growing global uncertainty (e.g. current global politics, emergencies like COVID, economic instability, rapid technological advancement), it is unclear which direction donors will take, i.e. an even greater focus on value for money and impact, and/or willingness to explore innovative approaches and learning in uncertain territory. Wasafiri’s approach for systems MEL builds on Systemcraft. This is a diagnostic and design tool for systems change, that has been used globally across a broad range of systems and interventions. This paper summarises our approach to MEL for systems change. It aims to provide a short introductory overview and form a ‘conversation starter’ to initiate a practical dialogue on current practices, experiences, and learnings with MEL for systems change. It introduces some concepts and appropriate tools for measuring systems change and poses some key questions for further discussion. We aim to engage with funders and practitioners working on complex problems who are in the process of or planning to develop their approach to and practices for MEL, who are interested to learn, share and explore. We welcome your inputs, either in response to this document, via a call, or during online webinars that we will convene in 2025.

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press Publication, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability -- The country context--Burundi from 1999 to 2014 -- Ingos in peacebuilding--globally unaccountable, locally adaptive -- International organizations in peacebuilding--globally accountable, locally constrained -- Bilateral development donors--accountable for global targets, not local change

Politically smart approaches to donor investment climate programming. A Guidance Note - LASER (Synthesis Paper, 1, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Politically smart approaches to donor investment climate programming (and annexes) Revised February 2016 - sets out practical advice on how to adopt a politically smart (which requires being both ‘politically informed’ and ‘politically astute’) approach to programming. The annexes include a traffic light matrix for initial high level analysis; a problem diary template with examples; and an example of a flexible theory of change for adaptive, large scale programming
Keywords: Practice

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?

Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents --> Main audience What is PEA, its role and purpose (Section 2) --> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) --> Core information for teams planning and using PEA How to ensure quality (Section 5) --> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) --> General information for all readers

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.

Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically

A Framework for Embedding Learning in Systems Change - Bertermann, Kecia; Coffman, Julia (Center for Evaluation Innovation, 2024)
This five-step framework, developed and tested by a foundation, embeds learning in emergent systems change strategies. It prioritizes the testing of hypotheses and assumptions, uses learning questions, and calls for examining both confirming and disconfirming evidence. --- A framework for embedding learning in systems change strategies and for testing strategic uncertainties. Learning and evaluation approaches that accompany systems change efforts need to fit with and support the emergent nature of this work. Systems change efforts call for examining, with evidence, the hypotheses and assumptions that undergird the work and regularly adapting in response to what is learned. They require staff to be highly engaged in testing their ideas by gathering evidence, interpreting it, and then acting on its implications. This brief presents a learning approach—referred to here as the Learning Framework—developed and tested by a foundation to support its systems change strategies. It is intended for other practitioners working on approaches for integrating learning with systems change efforts. Because a wealth of conceptual work exists about why learning is critical to systems change but practical advice about how to do it is much less available, we describe the approach we took and how the Framework’s core elements fit together in practice. The primary purpose of this approach is to interrogate our strategic uncertainties. This approach to learning is different from the dominant approach to learning and evaluation in philanthropy that primarily looks for evidence (often static metrics) that expected outcomes have been achieved (an approach that is more suitable for linear and predictable change strategies). This Learning Framework is driven by, and organized around, hypotheses and assumptions. This is especially important for systems change efforts where the path forward cannot be determined with complete certainty, but where robust evidence collection and regular sensemaking can increase our confidence in chosen directions and ultimately increase our chances of success.

PFM Reform Through PDIA: What Works and When it Works - Harris, Jamelia; Lawson, Andrew (Public Financial Management Blog - IMF, 2022)

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

Overcoming Premature Evaluation - Roche, Chris (2016)
Guest post from Chris Roche on practical ways of introducing adaptive management, learning from failure etc in aid programmes

The Art and Craft of Bricolage in Evaluation - Aston, Thomas; Apgar, Marina (CDI Practice Paper, 2022)
This CDI Practice Paper by Tom Aston and Marina Apgar makes the case for ‘bricolage’ in complexity-aware and qualitative evaluation methods. It provides a framework based on a review of 33 methods to support evaluators to be more intentional about bricolage and to combine the component parts of relevant methods more effectively. It discusses two cases from practice to illustrate the value added of taking a more intentional approach. It further argues that navigating different forms of power is a critical skill for bricolage, and that doing so can help to ensure rigour.

The process approach to projects - ODA (Overseas Development Administration, 1989)

Guidance: Rigor and Reproducibility in Grant Applications | grants.nih.gov - NIH (National Institutes of Health, 2018)

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS Policy Briefing, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT

Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning

Using what we know: How to ensure tech projects meet the brief - Walker, Tom (Making All Voices Count, 2017)
Making tech effective - building on what we already know

A ‘real-time’ and anthropological response to the Ebola crisis - IDS (IDS, 2017)
Impact Summary The Ebola epidemic that began in the Guinea-Sierra Leone-Liberia border region in December 2013 spread fast through the villages, cities and trade routes of this highly-peopled,...

Barrio Mio and Katye: PCI’s neighbourhood approach in cities - Campbell, Leah (AKNAP case study, 2019)

Assumption-aware tools and agency; an interrogation of the primary artifacts of the program evaluation and design profession in working with complex evaluands and complex contexts - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
Like artisans in a professional guild, we evaluators create tools to suit our ever evolving practice. The tools we use as evaluators are the primary artifacts of our profession, reflect our practice and embody an amalgamation of paradigms and assumptions. With the increasing shifts in evaluation purposes from judging program worth to understanding how programs work, the evaluator’s role is changing to that of facilitating stakeholders in a learning process. This involves clarifying purposes and choices, as well as unearthing critical assumptions. In such a role, evaluators become major tool-users and begin to innovate with small refinements or produce completely new tools to fit a specific challenge or context. We interrogate the form and function of 12 tools used by evaluators when working with complex evaluands and complex contexts. The form is described in terms of traditional qualitative techniques and particular characteristics of the elements, use and presentation of each tool. Then the function of each tool is analyzed with respect to articulating assumptions and affecting the agency of evaluators and stakeholders in complex contexts.
Keywords: Agency; Assumption-aware; Complex context; Complex programs; Participatory approaches; Program design; Program evaluation; Program tools; Theory-based

Smart Implementation of complex change processes - Beier, Christoph; Kirsch, Renate (Global Solutions Journal, 2020)
Cooperation management facilitates the recoupling of progress toward sustainable development

Crisis relief for adults & families everywhere - Featuring the mighty micro-VCoL - Lectica (Lectica Live, 2020)
In response to the COVID-19 pandemic and the resulting economic crisis, we're open-sourcing our most effective stress- and crisis-management learning tools. We call these tools micro-VCoLs™. All of the micro-VCoLs shared here can be practiced effectively just by following the instructions.

The principle of the hiding hand - Hirschman, Albert O. (National Observer, 1967)

Good Enough Governance Revisited - Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Still watering white elephants? The blueprint versus process debate thirty years on - Booth, David (Perspectives on politics, production and public administration in Africa: essays in honour of Ole Therkildsen, 2015)

Impact assessment and the quest for the Holy Grail - Bymolt, Roger (KIT Working papers, 2015)

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

AID Programming Guide - DFAT (Australian Government, 2019)

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (Practice Paper, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

Rapid Results!: How 100-Day Projects Build the Capacity for Large-Scale Change - Schaffer, Robert H.; Ashkenas, Ron (Jossey-Bass, 2005)
Rapid Results! shows how to make large-scale changes succeed  by using 100-day results-producing projects to develop this vital implementation capability. Written by Robert H. Schaffer, Ronald N. Ashkenas, and their associates—leaders in the field of change management—Rapid Results! describes an approach that has been field-tested by real organizations of every size and description to improve performance and speed the pace of change. Rapid results projects produce results quickly, introduce new work patterns, and enable participants to learn a variety of lessons about managing change. Step by step, the book describes how the use of rapid-cycle, or 100-day, projects   will multiply your organization’s power to succeed at large-scale change. Schaffer and Ashkenas specifically outline the concept behind 100-day projects and show you how to Set up the architecture to implement rapid results projects Improve operational performance and also attain hard results in the soft areas of management Build rapid results into major organizational change such as reorganization, acquisition integration, and international development Use rapid results to drive leadership development and culture change

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (M&E Paper 10, 2016)

A Refresher on Discovery-Driven Planning - Gallo, Amy (Harvard Business Review)

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

Fast Isn’t the Same as Forward - Brink (Brink's Cognitive Download, 2025)
What it takes to create smart velocity

The Dynamics of Team Learning: Harmony and Rhythm in Teamwork Arrangements for Innovation - Harvey, Jean-François; Cromwell, Johnathan R.; Johnson, Kevin J.; Edmondson, Amy C. (Administrative Science Quarterly, 2023)
Innovation teams must navigate inherent tensions between different learning activities to produce high levels of performance. Yet, we know little about how teams combine these activities—notably reflexive, experimental, vicarious, and contextual learning—most effectively over time. In this article, we integrate research on teamwork episodes with insights from music theory to develop a new theoretical perspective on team dynamics, which explains how team activities can produce harmony, dissonance, or rhythm in teamwork arrangements that lead to either positive or negative effects on overall performance. We first tested our theory in a field study using longitudinal data from 102 innovation teams at a Fortune Global 500 company; then, we replicated and elaborated our theory in a study of 61 MBA project teams at an elite North American university. Results show that some learning activities can occur within the same teamwork episode to have harmonious positive effects on team performance, while other activities combine to have dissonant negative effects when occurring in the same episode. We argue that dissonant activities must be spread across teamwork episodes to help teams achieve a positive rhythm of team learning over time. Our findings contribute to theory on team dynamics, team learning, and ambidexterity.

RFI-521-17-000015 - Improving Governance in Haiti Program (IGHI) - USAID (USAID, 2017)

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (Evaluation Checklists Projects, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve

Requisite Variety and Its Implications for the Control of Complex Systems - Ashby, W. Ross (Cybernetica, 1958)

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)

Learning From Failure 2020 - What CARE’s evaluations tell us about how to improve our work - CARE (CARE, 2020)
“Ever failed. No matter. Try again. Fail again. Fail better.” --Samuel Beckett Here’s my favorite part of that quote: the ultimate goal is not a lack of failure; it’s better failures. That’s good news for CARE, because we just published round two of our Learning From Failure initiative, and…I know this will surprise everyone…we haven’t stopped failures yet. We do have some hopeful signs that we’re failing better; or at least, that we’re improving on some concrete weaknesses we identified in the first round. It’s an interesting process to launch the second phase of learning from failure. The first round, we didn’t know what we were going to find. We spent as much time talking about how it was the first-ever report of its kind as we did about the actual failures. Our case study admitted, “It's still very early to see specific development impacts.” Round two isn’t quite the same. It’s not new anymore, so there’s less excitement at having invented something. We’re not discovering data and themes for the first time. In a lot of ways, the stakes are higher. Round two of learning from failure becomes an exercise in continuous performance improvement, rather than a journey of discovery. If we don’t see improvements, we don’t have the excuse that it’s too early to tell. It also takes a sustained commitment. Launching an exploratory exercise at a small scale is easy, especially when no one quite knows what the answers will be. Pulling together a few pieces of content over a few months is pretty straightforward. It takes some staying power—and real support from leadership—to keep up the work over time, especially in the middle of a pandemic. That’s even more true once we’ve seen one round of results and had a chance to understand the work that it takes to improve.

Behavioral Design: A New Approach to Development Policy - Datta, Saugato; Mullainathan, Sendhil (Review of Income and Wealth, 2014)

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry; Patten, Michael Quinn (IDRC Books, 2001)
"Outcome Mapping provides not only a guide to essential evaluation map-making, but also a guide to learning and increased effectiveness, and affirmation that being attentive along the journey is as important as, and critical to, arriving at a destination." - Michael Quinn PattonMore and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. "Outcome Mapping" recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, "Outcome Mapping" debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.

Thinking and working politically: What have we learned since 2013 - Teskey, Graham (TWP Community of Practice, 2021)
The Thinking and Working Politically (TWP) Community of Practice (CoP) was established at a small meeting tacked on at the end of a meeting of Governance Advisers working for the United Kingdom’s Department of International Development (DFID) on South and South-East Asian countries, held in Delhi in November 2013. Since then, a number of meetings have been held throughout the world, each addressing different issues; ‘TWP’ has entered the lexicon of mainstream development; the CoP has expanded to more than 300 people; a Washington DC chapter has been established; and the International CoP has been granted modest funding from DFID’s successor, the Foreign, Commonwealth and Development Office (FCDO) and from Australia’s Department of Foreign Affairs and Trade (DFAT). It is legitimate to ask, however, what has been achieved operationally: how have the ideas underpinning TWP affected operational practice? This short paper traces the evolution of the idea and practice of TWP from 2013 to late 2021, and identifies what we have learned. What has been successful, and what has not? I asked in 2017 whether TWP had become a second orthodoxy (Teskey, 2017). Did this represent hubris or was 2017 in some ways the apogee of what might rather grandly be called the TWP ‘movement’?

Knowledge Retention and Transfer (KRT) - Model overview presentation - USAID (USAID, 2023)
What problem is the KRT model trying to solve? For workforces that experience continuous staff turnover, the lack of systematic knowledge transfer can often lead to: - Loss of programmatic momentum, - Duplication of efforts and frustration, and - Wasted time and resources. The Knowledge Retention and Transfer (KRT) model provides tools, processes, and practices to individuals, teams, offices, and organizations to improve knowledge handover, which in turn improves efficiency and programmatic and operational learning.

Knowledge Retention and Transfer (KRT) - Model and Matsurity Matrix - USAID (CLA Toolkit, 2019)
The Maturity Matrix is not a standalone tool. It is one of the three major components of the KRT Model. The Maturity Matrix is meant to be used in conjunction with the KRT Toolkit and Implementation Plan.

The Boda Boda Talk Talk Module - Internews (Learning Collection, 2017)
Keywords: IMPORTANT

Evaluation of development programmes - OECD - OECD (2019)
Data & research on evaluation of development programmes inc. paris declaration, budget support, multilateral effectiveness, impact evaluation, joint evaluations, governance, aid for trade

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

Transforming our work: Getting ready for transformational projects - Kehrer, Daniel; Flossmann-Kraus, Ursula; Ronco Alarcon, Sabrina Valeria; Albers, Vivien; Aschmann, Gwendolin (GIZ, 2020)

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)

ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

The Learning Power of Listening - Guijt, Irene; Gottret, Maria Veronica; Hanchar, Anna; Deprez, Steff; Muckenhirn, Rita (PRACTICAL ACTION PUBLISHING, 2022)
Steff had the pleasure to co-author the first SenseMaker Practitioner Guide with a group of friends and colleagues supported and published by Oxfam and CRS. This practical guide is for those who wish to use SenseMaker to conduct assessments, monitor progress, and undertake evaluations or research. Drawing on more than a decade of experience, the authors share dozens of examples from international development, providing practical tips and ideas for context-specific adaptations. They show how the method can be used to for difficult-to-measure outcomes related to poverty reduction, social justice, peacebuilding, resilience, gender norms, behavior change, governance and environmental management. ​ SenseMaker is a unique participatory method of inquiry that encourages and enables novel insights not obtained from conventional quantitative and quantitative and qualitative methods. It is action-oriented and, therefore, well-suited for people needing data- informed insights for adaptive management. "Writing this guide together with Irene, Veronica, Anna and Rita was an enormous learning process in itself and has further shaped our thinking and practice. We hope it will support first-time and experienced users to enhance their practice and that it will inspire people to explore and innovate further with the method."

Program Cycle Road Map - USAID (2016)

Learning and Results in World Bank Operations: Toward a New Learning Strategy - World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

Discovery-Driven Planning - McGrath, Rita; MacMillan, Ian (Harvard Business Review)

Strategy Testing: An innovative approach to monitoring highly flexible aid programs - Ladner, Debra (Working Politically in Practice, 2015)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.

Effective Governance. Strategy for Australia’s aid investments - DFAT (Department of Foreign Affairs and Trade, Australian Government, 2015)

Forward Look - A vision for the World Bank Group in 2030 - World Bank (World Bank, 2016)

Strategic Framework for mainstreaming citizen engagemente in World Bank Group operations - World Bank (The World Bank, 2014)

Development as Process: Concepts and Methods for Working with Complexity - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be more flexible and offer greater prospects of success than traditional "project" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine development projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-agency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources development in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Keywords: Demography; Economic Development; Sociology

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Prospects practice paper, 4, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (2019 CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

Forget the money: De-linking technical assistance - Manuel, Clare (Synthesis Paper, 4, 2016)

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Working Paper 322, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Supporting Learning? Exploring the relationship between grantee learning and grantmaking practice in the transparency and accountability sector - Ross, Jenny (INTRAC, 2015)
Learning is fundamental to work on transparency and accountability in complex environments. But how can funding practices best support learning?

Virtuous cycles of learning: Using formative, embedded, and diagnostic developmental assessments in a large-scale leadership program - Stein, Z.; Dawson, Theo; Van Rossum, Zachary; Rothaizer, Joel; Hill, S. (Journal of Integral Theory and Practice, 2014)
This article presents preliminary results from a series of ongoing action-research projects involving the use of embedded diagnostic developmental assessments (called LectaTests™) in leadership education contexts. These findings are presented to support a particular metatheoretical approach to learning and education in which embedded assessments form a crucial part of ongoing virtuous cycles of action, feedback, support, and learning. We present two types of evidence. First, we compare developmental growth across eight program evaluations in which LectaTests were and were not embedded. Second, we examine how embedding LectaTests in a large-scale leadership development program affected the growth of managers and their direct reports. We review these findings with an eye toward detecting the benefits of using developmental assessment as embedded diagnostics alongside their use as research instruments. We begin by using Integral Theory to structure a discussion about the ideal function of developmental assessments in educational contexts.

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

Guidance Note: Evaluation Criteria - Chaplowe, Scott; Child, Keith; AF-TERG (Adaptation Fund, 2024)

Anatomy of Social Accountability 3.0: A working framework for moving forward - Guerzovich, Florencia; Aston, Tom (Florianopolis, SC, Brazil: Grupo Politeia, ESAG, University of the State of Santa Catarina and act4delivery, 2023)
This note presents the key components of a potential next generation of social accountability programming. The key aspects outlined emerge from a review of over 150 cases as well as tacit knowledge from dozens of practitioners (Guerzovich and Aston, 2023).The main thread of social accountability 3.0 and what distinguishes it from previous generations is a focus on its contribution towards more responsive systems and accountable social contracts. In particular, social accountability should be considered as an operational means to rework social contracts.Over the last two decades, the field has been defined by a supposed dichotomy between minimalist (i.e., “widget” based) approach or a maximalist (“go big or go home”) approaches. Yet, most practice sits somewhere between these extremes. The paper presents various options derived from practice; practitioners should choose whichever best fits their own particular circumstances.Those hoping to improve and expand their practice with a systems-lens may benefit from considering how they approach the key elements of social accountability 3.0.
Keywords: accountability; development; responsiveness; social accountability; social contract; systems

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

Applied political economy analysis for human rights programs and campaigns: A guide for practitioners (second edition) - Pact (Pact, 2023)
This updated guide provides practical guidance to practitioners in the human rights sector and beyond on how to integrate Applied Political Economy Analysis

Scenario-based strategizing: Advancing the applicability in strategists' teams - Lehr, Thomas; Lorenz, Ullrich; Willert, Markus; Rohrbeck, René (Technological Forecasting and Social Change, 2017)
For over 40years, scenarios have been promoted as a key technique for forming strategies in uncertain environments. However, many challenges remain. In this article, we discuss a novel approach designed to increase the applicability of scenario-based strategizing in top management teams. Drawing on behavioural strategy as a theoretical lens, we design a yardstick to study the impact of scenario-based strategizing. We then describe our approach, which includes developing scenarios and alternative strategies separately and supporting the strategy selection through an integrated assessment of the goal-based efficacy and robustness. To facilitate the collaborative strategizing in teams, we propose a matrix with robustness and efficacy as the two axes, which we call the Parmenides Matrix. We assess the impact of the novel approach by applying it in two cases, at a governmental agency (German Environmental Ministry) and a firm affected by disruptive change (Bosch, leading global supplier of technology and solutions).
Keywords: Behavioural strategy; Scenario-based strategizing; Scenarios; Strategic foresight; Uncertainty

Re-institute website - RE!NSTITUTE (Re!nstitute, 2023)
We are a dynamic non-profit organization with a unique approach to managing change and catalyzing innovation to support global systems transformation. We know that to achieve equal, just, and safe communities, we must collectively challenge and change the systems that people rely on — especially those most vulnerable. Together, we must RE!BUILD a system's resilience and capacity to take on our biggest generational challenges. Justice, housing, health, and other systems in every country are often struggling to come together, across institutions and organizations, to unite under a common vision for change, and implement those changes in effective and innovative ways. Our work and methodology — the 100-Day Challenge — are designed to support these systems to achieve extraordinary results. Our approach is rooted in the philosophy that frontline staff, supported by leadership, can unleash innovation and achieve incredible results by creating new relationships, experimenting with fresh ideas from across their system, and building authentic engagement with those with lived experience.

Evaluative Inquiry for Systemic Change: A Guide to Shift Beyond Fixes to Lasting Value - Gates, Emily F.; Vidueira, Pablo (SAGE Publications, Inc, 2025)
In a world where social, ecological, health, and other problems are influenced by multiple, intersecting systems, why do most interventions target single-factor solutions? Why does so much evaluation settle for incremental change, and how could it contribute instead to deeper, lasting, transformative change? Authors Emily F. Gates and Pablo Vidueira make two interconnected arguments in this book: they critique the "fixed" approach of traditional program evaluation and policy analysis, and they advance an alternative approach centered on changing systems and developing the value of efforts toward change. They demonstrate that systemic change that embeds evaluative inquiry is a theoretically supported, practical way to work toward fundamental social change with lasting impact.

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

The Future is a Choice: The Oxfam Framework and Guidance for Resilient Development - Jeans, Helen; Thomas, Sebastien; Castillo, Gina (Policy & Practice, 2016)
This guide provides a framework for Oxfam staff to design programmes and campaigns that contribute to resilient development. Oxfam defines resilience as ‘the ability of women and men to realize their rights and improve their well-being despite shocks, stresses

Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Complexity-Aware Monitoring and Evaluation - Hertz, Tilman; Brattander, Eva; Rose, Loretta (Journal of MultiDisciplinary Evaluation, 2021)
Background: Addressing today’s sustainability challenges requires adopting a systemic approach where social and ecological systems are treated as integrated social-ecological systems. Such systems are complex, and the international development sector increasingly recognises the need to account for the complexity of the systems that they seek to transform. Purpose: This paper sketches out the elements of a complexity-aware monitoring and evaluation (M&E) system for international development programmes in the area of sustainable development.  Setting: Not applicable. Data Collection and Analysis: The authors draw on existing literature on complexity and evaluation and on their own experience from working in the field of M&E. Findings: An M&E system should not be seen simply as a tool to track compliance against a pre-determined theory of change. Instead, it is most useful as a real-time approach, constantly defining and re-defining narratives for change that help push systems along trajectories of interest. Dealing with complexity involves embracing uncertainty; and this challenges established notions of accountability—something which funders and implementers must begin to redefine together. Keywords: monitoring; evaluation; complexity; social-ecological systems; international development programmes; narratives for change; theory of change

Whose Reality Counts? Putting the First Last - Chambers, Robert (ITDG Publishing, 1997)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.Development professionals now need new approaches and methods forinteracting, learning and knowing. Through analyzing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions.In many countries, urban and rural people alike have shown an astonishing ability to express and analyze their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Self-critical awareness and changes in concepts, values, methods and behaviour must be developed to explore the new high ground of participation and empowerment."Whose Reality Counts?" presents a radical challenge to all concernedwith development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies. With its thrust of putting the first last it presents a new, exciting and above all practical agenda for future development which cannot be ignored.

Thinking and Working politically to support developmental leadership and coalitions: The Pacific Leadership Program - Denney, Lisa; McLaren, Rebecca (Research Paper, 2016)

Track to Change | Home - Clear Horizon (Clear Horizon, 2025)
Track to Change homepage

How DFID learns - ICAI (Independent Commission for Aid Impact (ICAI), 2014)
Excellent learning is essential for UK aid to achieve maximum impact and value for money. We take learning to mean the extent to which DFID uses information and experience to influence its decisions. Each ICAI review assesses how well learning takes place. Our reports to date indicate a mixed performance. This review seeks to identify the way DFID learns and what inhibits it from doing so consistently. We drew on our reviews, assessed data from DFID’s own surveys and carried out interviews inside and outside the department. Review DFID generates considerable volumes of information, much of which, such as funded research, is publicly available. DFID does not clearly or consistently link this investment to how it can deliver better impact. We made five recommendations and gave an amber-red score. Findings DFID does not clearly identify how its investment in learning links to its performance and delivering better impact. DFID has the potential to be excellent at organisational learning if its best practices become common. DFID staff learn well as individuals. They are highly motivated and DFID provides opportunities and resources for them to learn. DFID is not yet, however, managing all the elements that contribute to how it learns as a single, integrated system. DFID does not review the costs, benefits and impact of learning. Insufficient priority is placed on learning during implementation. The emphasis on results can lead to a bias to the positive. Learning from both success and failure should be systematically encouraged. Recommendations DFID needs to focus on consistent and continuous organisational learning based on the experience of DFID, its partners and contractors and the measurement of its impact, in particular during the implementation phase of its activities. All DFID managers should be held accountable for conducting continuous reviews from which lessons are drawn about what works and where impact is actually being achieved for intended beneficiaries. All information commissioned and collected (such as annual reviews and evaluations) should be synthesised so that the relevant lessons are accessible and readily usable across the organisation. The focus must be on practical and easy-to-use information. Knowhow should be valued as much as knowledge. Staff need to be given more time to acquire experience in the field and share lessons about what works and does not work on the ground. DFID needs to continue to encourage a culture of free and full communication about what does and does not work. Staff should be encouraged always to base their decisions on evidence, without any bias to the positive.

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Release the pressure on governance practitioners - de Weijer, Frauke; Hauck, Volker (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Improving development aid design and evaluation: Plan for sailboats, not trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT

Measuring Impact. Making Use of the Portfolio: Organizational Learning at USAID - Peabody, Shawn (Measuring Impact, 2015)
This technical analysis explores previous and ongoing social learning efforts, best practices, challenges, and lessons in USAID as a foundation for improving the implementation and design of the Agency’s forestry and biodiversity programs. This analysis is particularly relevant as the Bureau of Economic Growth, Education and the Environment’s Office of Forestry and Biodiversity (E3/FAB) begins to develop a Cross-Mission Learning Program under the Measuring Impact initiative, a five-year activity to promote the adoption of best practices in the USAID program cycle among Missions using biodiversity funds. The findings reported in this document can help inform the overall design and structure of the Learning Program and provide insight into possible challenges and best practices.

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.

Resilience Thinking: Sustaining Ecosystems and People in a Changing World - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, ecosystems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: more control, more intensification, and greater efficiency. "Resilience thinking" offers a different way of understanding the world and a new approach to managing resources. It embraces human and natural systems as complex entities continually adapting through cycles of change and seeks to understand the qualities of a system that must be maintained or enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a constructive alternative that opens up options rather than closing them down. In "Resilience Thinking", scientist Brian Walker and science writer David Salt present an accessible introduction to the emerging paradigm of resilience. The book arose out of appeals from colleagues in science and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices. Rather than complicated theory, the book offers a conceptual overview along with five case studies of resilience thinking in the real world. It is an engaging and important work for anyone interested in managing risk in a complex world.

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

Everyday Political Analysis - Hudson, David; Marquette, Heather; Waldock, Sam (Developmental Leadership Program, 2016)
This short note introduces a stripped-back political analysis framework designed to help frontline development practitioners make quick but politically-informed decisions. It aims to complement more in-depth political analysis by helping programming staff to develop the 'craft' of political thinking in a way that fits their everyday working practices. Everyday Political Analysis involves two steps: Understanding interests: What makes people tick? Understanding change: What space and capacity do people have to effect change? For each step five questions, accompanied by prompts, aim to help staff to conduct quick political analysis. The EPA framework can be used at any stage of the aid management cycle, and can help users to respond rapidly to unexpected change. We are keen to hear back from people on their experience of using EPA to help us adapt the framework. Was it useful (or not)? Do people tend to use just one or both steps? Are there missing statements or prompts that would improve the analysis? Please email us at info [at] dlprog.org.

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Governance Working Paper 1, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

The Art of Scaling Deep - Research in Summary - Fraser, Tatiana (The Systems Sanctuary, 2023)
Over the last 15 years the concept of scale has become a foundational part of the apparatus of the social and environmental change sector. A business mindset of growth has been seamlessly transferred to the social and environmental problems we are collectively trying to shift in the world. Scaling up, (influencing policy) has been considered the strategic pathway to systems change. Scaling out (spreading new models) is seen as a pathway to success. The allure of these scaling theories lies, in part, in their tangibility, and the easy way in which they can be measured. However this focus on growth has shifted our attention away from a series of messy truths. Sometimes bigger isn't better. Endless growth is not sustainable and our urgency to try to fix the problem and seek solutions may be part of the crisis we are in. One unintended consequence of this has been that another type of scale has been devalued and as a result, under-resourced. It’s a scale that values the slow steady work of deepening relationships. It recognizes the significance of context, building connections that bridge diverse communities and it prioritizes inner work and healing as integral components of the scaling process. We call this type of scale ‘Scaling Deep’ and we believe that adequately supporting it, and funding it, holds the greatest potential for long lasting systemic change. The purpose of this research has been to delve deeper into the art and craft of Scaling Deep. Ultimately, our goal is for it to become firmly ingrained within the recognized realm of social change, alongside the well-established concepts of scaling up and scaling out. We want practitioners who are Scaling Deep to be able to harness the wisdom and power of this work and to talk about it openly, with confidence and credibility. We want understanding of this approach to flourish and evolve and for it to be appropriately celebrated and supported. We want decision-makers to be informed and inspired by the principles and practices of scaling deep. For it to be embedded in theories of change as an essential component of decision-making processes within the wider change discourse. Importantly we want leaders who are Scaling Deep to have access to sufficient resources and to receive the care from the field that they need to thrive. We would like to see organisations that have the power to invest, to align their efforts with the profound impact that scaling deep aspires to cultivate in the world. Before we begin, let us be crystal clear. We are not opposed to scaling up and out as strategies for change. Innovation and scaling what is working is part of how we evolve as humanity. As social entrepreneurs ourselves, we have both done this twice over. We value it and we know it’s important. We recognize these are strategies for creating widespread impact and effecting positive change. Our intention here is not to dismiss or undermine the value of scaling up and out, but rather to encourage a broader and more holistic perspective that includes other dimensions of scale. There is a need to understand how the different scaling approaches can work together, rather than seeing them as hierarchical and disconnected. Our ultimate goal is to equip the change sector with a more inclusive, expansive, and powerful approach to tackling the myriad challenges we face, by exploring the potential of Scaling Deep as a transformational strategy for systems change.

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (Working Paper, 2014)

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (Synthesis Paper, 1, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice

Investment Climate Reform: Doing it Differently - Manuel, Clare (Synthesis Paper, 1, 2015)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). First synthesis paper - Investment climate reform: doing it differently June 2015 Drawing on our experience in taking a problem-focused approach to investment climate reform, we discuss in this peer-reviewed paper emerging lessons and reflections on what works, both in recent literature and in practical experience.

DFID Smart Rules: Better Programme Delivery - version VII (2017.04) - DFID (DFID, 2017)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

DFID Smart Rules: Better Programme Delivery - version VI (2016.10) - DFID (DFID, 2016)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Understanding innovation, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"--Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations

It's the politics! Can donors rise to the challenge? - Unsworth, Sue (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

Thinking and Working Politically in development - Coalitions for Change in The Philippines - Sidel, John T.; Faustino, Jaime (The Asia Foundation, 2020)
The Asia Foundation and the Australian Embassy in the Philippines today released a new publication, Thinking and Working Politically in Development: Coalitions for Change in the Philippines. Written by London School of Economics and Political Science Professor John T. Sidel and The Asia Foundation’s Jaime Faustino, the book examines the first phase of the Coalitions for Change program (2012-2018) and the contributions to key development policy reforms in the Philippines. The book is a rigorous treatment of the Coalitions for Change program’s transformative policy reforms—alongside lessons from its failures—across diverse policy arenas and in a wide variety of cities and provinces. The chapters are organized thematically: excise tax reform (Chapter 2), land governance reform (Chapter 3), education (Chapter 4), electoral reform (Chapter 5), disaster risk reduction and management (Chapter 6), and subnational governance reform and conflict resolution in Mindanao (Chapter 7). The co-authors together combine an independent, academic perspective on the program’s impacts (Sidel) with a front-row view of doing policy reform in the Philippines – both its political and technical dimensions (Faustino). Based on the empirical research and comparative analysis undertaken by the authors, the book articulates – and substantiates – a strong set of arguments that help to explain the program’s mixed pattern of achievements and disappointments. Overall, the book concludes that the seven-year program achieved significant and sustainable impact using problem-driven, adaptive, and iterative approaches to developmental change. The authors assert the program was at the forefront of notable development approaches: aid effectiveness and development around thinking and working politically, doing development differently, and adaptive programming. Graham Teskey, an early advocate of ‘thinking and working politically’ explores how development agencies can replicate the conditions for success in his Afterword. With illustrative case studies and analyses, the book provides valuable lessons for policymakers, scholars, bilateral agencies, think-tanks, and anyone interested in successfully maneuvering the shifting dimensions of development in the Philippines and elsewhere.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (Complexity and Development Seminar Series, 2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.

Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalable inclusive change interventions, as well as how to plan and manage the scale-up process. Focusing on interventions with the aim of reaching the most marginalised and transform social norms, it covers programmes aiming to deliver inclusive outcomes for women and girls (with a particular focus on preventing violence against women and girls) and persons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-scale projects. There are limited experiences of scale-up and fewer evaluations of these experiences. However, there are some documented case studies as well as emerging analysis that draw out lessons learned. From this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic approach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political support for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping points, diffusion effects, and local champions 5. Locally grounded, participatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up strategies 8. Measuring impact and sustainability.

Mind the gaps: What's missing in political economy analysis and why it matters - Hudson, David; Marquette, Heather (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Complexity Leadership Theory (CLT) - Abbaszada, Ramiz (2022)
The present literature review was conducted in order to investigate the role of Complexity Leadership Theory (CLT) in modern public administration. We use data from different academic articles to decompose the value within the framework of this theoretical perspective. In addition to explaining how extend, Complexity Leadership Theory (CLT) is crucial in the “information age” and its main factors will be the main priorities of the study. Traditional top-down conceptions of leadership are at best unduly simplistic, as twenty-first-century management continues to stress decentralized organizing structures and co-evolutionary ecologies of enterprises, institutions, and markets. There's also a growing recognition that effective leadership isn't always defined by the leader's symbolic, motivating, or charismatic behaviors. But, if leadership isn't "in" or "done by" a leader, how can we understand what leadership is and where it comes from? A unique method to answering these concerns is based on complexity theory, specifically the idea that leadership emerges from relational interactions among actors. Leadership, in this view, is more than a talent, a transaction, or a symbol; it comes from dynamic relationships. The role of leadership in accelerating those processes in companies where interdependent acts among many persons merge into a collective venture is investigated by "complexity leadership theory." Complexity leadership is a combination of the three forms of leadership described below: (1) administrative leadership based on tight control and a large bureaucratic hierarchy (2) adaptive leadership, which is built on creative issue solution, resonating with changing situations, and learning, and (3) action-centered leadership, which entails crisis decision-making and dynamic productivity.

Theory of Change Thinking in Practice - van Es, Marjan; Guijt, Irene; Vogel, Isabel (2015)
Want to know better how your interventions can contribute to change? A Theory of Change (ToC) approach helps in deepening your understanding - and that of your partners - of how you collectively think change happens and what the effect will be of your intervention. Not only does it show what political, social, economic, and/or cultural factors are in play, it also clarifies your assumptions. Once a ToC has been developed, it can be used to continually reflect on it in ways that allow for adaptation and checking of assumptions of your intervention. This user friendly guideline helps you to use a Theory of Change approach. Theories of change are the ideas and beliefs people have – consciously or not – about why and how the world and people change. How people perceive and understand change and the world around them is infused by their underlying beliefs about life, human nature and society. They are deep drivers of people’s behaviour and of the choices they make. Social change processes are complex and characterised by non-linear feedback loops: our own actions interact with those of others and a myriad of influencing factors. This triggers reactions that cannot be foreseen and makes outcomes of change interventions unpredictable. Given these uncertainties, how can we plan strategically and sensibly? How can social change initiatives move forward in emerging change processes in a flexible way, while remaining focused on the goal? In this context of complexity, Hivos has found a theory of change (ToC) approach useful in guiding its strategic thinking and action, as well as its collaborative efforts with others. As it fosters critical questioning of all aspects of change interventions and supports adaptive planning and management in response to diverse and quickly changing contexts. It contributes to the quality and transparency of strategic thinking, and therefore to personal, organisational and social learning. This guide builds on the experiences of Hivos working with a ToC approach. It is a practical guide for Hivos staff in applying a Theory of Change approach, but is also very useful for others working on social change such as social entrepreneurs and innovators. This guide builds on the work of a ToC Learning Group initiated by Hivos and comprising of staff of the Centre for Development Innovation (CDI) of Wageningen University and Research Centre and of experts Iñigo Retolaza Eguren, Isabel Vogel and Irene Guijt. For current thinking and work on the use of Theory of Change thinking in complex change processes, see http://www.theoryofchange.nl

Participation for Humanitarian Innovation - Toolkit - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

Participation for Humanitarian Innovation - Background Paper - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

A Pragmatic Approach to Assessing System Change - Posthumus, Hans; Shah, Rachel; Miehlbradt, Alexandra; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

A Pragmatic Approach to Assessing System Change: How to put it into practice - Miehlbradt, Alexandra; Shah, Rachel; Posthumus, Hans; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.